Conductive composition

By using conductive compositions of carbon nanotubes, copolymers and water-based solvents in lithium-ion batteries, the problem of easy aggregation of carbon nanotubes in water-based solvents is solved, and the battery performance improvement and environmentally friendly manufacturing process is achieved.

JP2025503528APending Publication Date: 2025-02-04GRST INTERNATIONAL LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024539251
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-12-28
Publication Date
2025-02-04

AI Technical Summary

Technical Problem

In the manufacturing process of existing lithium-ion batteries, the use of organic solvent NMP leads to high costs and environmental pollution, and carbon nanotubes are prone to aggregation in water-based solvents, making it difficult to effectively disperse in battery manufacturing.

Method used

Using a conductive composition containing carbon nanotubes, copolymers and water-based solvents, the copolymers and carbon nanotubes are uniformly dispersed in the water-based solvent to form a stable conductive composite.

Benefits of technology

Effective dispersion of carbon nanotubes in water-based solvents is achieved, manufacturing costs are reduced, battery performance is improved, and environmental problems caused by the use of organic solvents are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503528000001_ABST
    Figure 2025503528000001_ABST
Patent Text Reader

Abstract

The conductive composition for secondary batteries includes a copolymer, carbon nanotubes (CNTs) and an aqueous solvent. The copolymer includes structural units (a), (b) and (c), and has excellent adhesion to the surface of the CNTs and high affinity to the aqueous solvent. As a result, the CNTs can be more uniformly dispersed in the aqueous solvent of the conductive composition, and the conductive composition can remain stable even after a considerable time has passed. Therefore, the CNTs can be more easily handled and adapted for use in various applications. The electrode slurry includes an electrode active material. Battery cells including electrodes prepared using such electrode slurries exhibit excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of batteries, and in particular to conductive compositions and slurries containing same for lithium ion and other batteries. [Background technology]

[0002] Over the past decades, lithium-ion batteries (LIBs) have been widely used in various applications, especially in consumer electronics, due to their excellent energy density, long cycle life, and high discharge capability. With the rapid market development of electric vehicles (EVs) and grid energy storage, LIBs with their high performance and low cost currently present one of the most promising options for large-scale energy storage devices.

[0003] Typically, electrodes for lithium-ion batteries are fabricated by casting an organic-based slurry onto a metal current collector. The slurry contains the electrode active material, conductive carbon, and a binder in an organic solvent. The binder, most commonly polyvinylidene fluoride (PVDF), dissolves in the solvent and provides good electrochemical stability and high adhesion to the electrode material and current collector. However, PVDF is only soluble in certain organic solvents such as N-methyl-2-pyrrolidone (NMP), which requires special handling because it is flammable and toxic.

[0004] During the drying process, an NMP recovery system must be installed to recover the NMP vapor. This requires a large capital investment and therefore represents a significant cost in the manufacturing process. The use of cheaper and more environmentally friendly solvents, most commonly water, is preferred in the present invention, as it eliminates the large capital cost of the recovery system. Attempts to replace the organic NMP-based coating process with a water-based coating process have been successful for the negative electrode. A typical water-based slurry for anode coating contains carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR). In a battery, the cathode is at high voltage. Most rubbers, including SBR, are stable only at the low voltage of the anode and decompose at high voltages. Therefore, water-based coating for the cathode is very difficult, as opposed to the anode.

[0005] It is worth noting that the above issues are not unique to lithium-ion batteries: other types of batteries, such as sodium-ion batteries, may face similar problems.

[0006] Carbon-based materials such as amorphous carbon, graphene, carbon black, carbon nanotubes (CNTs), carbon nanofibers, and fullerenes have been widely used as conductive agents in this field due to their excellent electrical properties and thermal conductivity. In particular, CNTs, tubular carbons with very high aspect ratios, are expected to be new conductive agents in various fields. CNTs consist of a carbon network in which carbon atoms in graphite sheets are arranged in a honeycomb pattern, and six interlocking carbon hexagons form a tubular structure. The outstanding mechanical and electrical properties of CNTs come from their quasi-one-dimensional structure and graphitic arrangement of carbon atoms. In addition, their high thermal conductivity facilitates heat dissipation during the charge / discharge cycle of the battery, improving the battery's performance at high and low temperatures, and therefore extending the service life of the battery.

[0007] However, due to the strong intermolecular interactions between CNTs, CNTs tend to aggregate and are difficult to disperse in most solvents. As a result, there are significant challenges in incorporating CNTs into manufacturing processes that require CNTs to be mixed into solvents, such as battery-related manufacturing processes. Despite the favorable properties of CNTs, the difficulties in processing and handling CNTs have hindered their widespread use in battery-related applications. Therefore, methods to enhance the dispersion of CNTs in solvents is an important area of ​​current research.

[0008] Korean Patent Application Publication No. 20190088330 discloses a method for producing a carbon nanotube-electrode active material composite powder for improving electrical conductivity and battery performance, and an electrode containing the same. To achieve uniform carbon nanotube dispersion, the carbon nanotubes are dispersed in N-methyl-2-pyrrolidone (NMP) solvent and stirred through a stirrer to prevent aggregation between the carbon nanotubes. A polymer binder, such as polyvinylidene fluoride (PVDF), may be further incorporated in the preparation of the electrode slurry. However, this method is limited in its application due to the use of a large amount of the expensive and toxic organic solvent NMP. To significantly reduce production costs and environmental impact, it is preferable to use an aqueous solution instead of an organic solvent, and therefore a water-based treatment is adopted in the present invention. Furthermore, the above method does not teach how to stabilize carbon nanotubes in an aqueous system.

[0009] In view of the above, the present inventors have conducted intensive research on this subject. It has been found that a novel conductive composition comprising CNTs, a copolymer, and an aqueous solvent is stable, and that the copolymer allows the CNTs to be well dispersed in the aqueous solvent of the conductive composition. As a result, improved conductivity of the conductive composition can be achieved. Furthermore, it has been found that batteries comprising electrodes fabricated using the conductive composition disclosed herein have improved performance. Summary of the Invention

[0010] The aforementioned needs are met by various aspects and embodiments disclosed herein. In one aspect, provided herein is a conductive composition for a battery, comprising a copolymer, CNTs, and an aqueous solvent.

[0011] In another aspect, provided herein is an electrode slurry for a battery, comprising an electrode active material and a conductive composition. In some embodiments, the slurry further comprises a conductive agent. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 represents a sample of the conductive composition of Example 1. [Figure 2a] 2a and 2b are images of a dried sample of the conductive composition of Example 1 at magnifications of 10,000 and 50,000, respectively. [Figure 2b] 2a and 2b are images of a dried sample of the conductive composition of Example 1 at magnifications of 10,000 and 50,000, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The term "electrode" refers to either a "cathode" or an "anode."

[0014] The term "positive electrode" is used interchangeably with cathode. Similarly, the term "negative electrode" is used interchangeably with anode.

[0015] The terms "polymeric material", "binder", "polymeric binder" or "binder material" refer to a compound, mixture of compounds, or polymer used to hold the electrode material and / or conductive agent in place and to deposit onto a metal part or current collector to form an electrode. In some embodiments, the polymeric material forms a colloid, solution, or dispersion in an aqueous solvent, such as water.

[0016] The term "conductive agent" refers to a material that has good electrical conductivity. Thus, conductive agents are often mixed with the electrode active material during the formation of the electrode to improve the electrode's electrical conductivity. In some embodiments, the conductive agent is chemically active. In certain embodiments, the conductive agent is chemically inactive.

[0017] The term "carbon nanotube" refers to hollow cylindrical carbon structures composed of a hexagonal lattice of carbon atoms, the diameter of which is typically measured in nanometers.

[0018] The term "polymer" refers to a compound prepared by polymerizing monomers of the same or different types. The generic term "polymer" includes the terms "homopolymer" as well as "copolymer."

[0019] The term "homopolymer" refers to a polymer prepared by polymerization of the same type of monomers.

[0020] The term "copolymer" refers to a polymer prepared by the polymerization of two or more different monomers.

[0021] The "weight average molecular weight" M of the polymer W is mathematically defined as follows:

[0022]

number

[0023] Here, N i is a specific molecular weight M i is the number of polymer molecules having

[0024] The term "aqueous solvent" refers to a solvent that is water or that contains water and one or more minor components, with water making up the majority of the solvent by weight.

[0025] The term "unsaturated" refers to a moiety having one or more units of unsaturation.

[0026] The term "alkyl" refers to a group of the general formula C obtained by removing a hydrogen atom from a saturated, unbranched or branched aliphatic hydrocarbon. n H 2n+1 where n is an integer. An alkyl group can be unsubstituted or substituted with one or more suitable substituents.

[0027] The term "alkenyl" refers to an unsaturated straight-chain, branched-chain, or cyclic hydrocarbon radical containing one or more carbon-carbon double bonds. Similarly, the term "alkynyl" refers to a monovalent group obtained by removing a hydrogen atom from any carbon atom of an unsaturated aliphatic hydrocarbon having at least one carbon-carbon triple bond. Alkenyl and alkynyl may be substituted or unsubstituted. Non-limiting examples of alkenyl include ethynyl, 3-methylpent-1-yn-3-yl(HC≡C-C(CH 3 )(C 2 H 5 Additionally, the term "enynyl" refers to a monovalent group obtained by removing a hydrogen atom from any carbon atom of an unsaturated aliphatic hydrocarbon having at least one carbon-carbon double bond and at least one carbon-carbon triple bond.

[0028] The term "alkoxy" refers to an alkyl group attached to a carbon chain through an oxygen atom. Non-limiting examples of alkoxy groups include methoxy, ethoxy, propoxy, butoxy, etc. Alkoxy groups can be substituted or unsubstituted.

[0029] The term "alkylene" refers to a divalent saturated hydrocarbon group obtained by removing two hydrogen atoms from a straight-chain or branched-chain saturated hydrocarbon. Examples of alkylene groups include methylene (—CH 2 ―), ethylene (―CH 2 CH 2 ―), isopropylene (―CH(CH 3 )CH 2-), and the like. Alkylene groups are optionally substituted with one or more substituents described herein.

[0030] The term "aryl" refers to an organic radical obtained by removing a hydrogen atom from a monocyclic or polycyclic aromatic hydrocarbon. Non-limiting examples of aryl groups include phenyl, naphthyl, benzyl, tolanyl, sexiphenyl, phenanthrenyl, anthracenyl, coronenyl, and tolanylphenyl. An aryl group can be unsubstituted or substituted with one or more suitable substituents.

[0031] The term "carbonyl" refers to --(C=O)--.

[0032] The term "acyl" refers to -(C=O)-Z, where Z is alkyl. The term "acyloxy" refers to -O-(C=O)-Z, where Z is alkyl.

[0033] The term "amide" refers to -NH(C=O)-R.

[0034] The term "aliphatic" refers to an organic functional group, compound, or class of compounds that does not contain any aromatic rings. Non-limiting examples of aliphatic functional groups include alkyl, alkenyl, alkynyl, and alkylene.

[0035] The term "aromatic" refers to an organic functional group, compound, or class of compounds that contains at least one aromatic ring and optionally contains heteroatoms or substituents. Examples of aromatic functional groups include, but are not limited to, phenyl, tolyl, biphenyl, o-terphenyl, m-terphenyl, p-terphenyl, naphthyl, anthryl, phenanthryl, pyrenyl, triphenylenyl, and derivatives thereof.

[0036] The term "substituted" when used to describe a compound or chemical moiety refers to at least one hydrogen atom of the compound or chemical moiety being replaced with a second chemical moiety. Examples of substituents include halogen; alkyl; heteroalkyl; alkenyl; alkynyl; enynyl; aryl; heteroaryl; hydroxyl; alkoxyl; amino; nitro; thiol; thioether; imine; cyano; amido; phosphonato; phosphine; carboxyl; thiocarbonyl; sulfonyl; sulfonamido; acyl; formyl; acyloxy; alkoxycarbonyl; oxo; haloalkyl (e.g., trifluoromethyl); carbocyclic cycloalkyl (e.g., cyclopropyl, cyclobutyl, cyclopentyl, or cyclohexyl), which may be monocyclic or fused or non-fused polycyclic, or heterocyclic cycloalkyl (e.g., cyclopropyl, cyclobutyl, cyclopentyl, or cyclohexyl), which may be monocyclic or fused or non-fused polycyclic. o-alkyl (e.g. pyrrolidinyl, piperidinyl, piperazinyl, morpholinyl or thiazinyl); carbocyclic or heterocyclic, monocyclic or fused or non-fused polycyclic aryl (e.g. phenyl, naphthyl, pyrrolyl, indolyl, furanyl, thiophenyl, imidazolyl, oxazolyl, isoxazolyl, thiazolyl, triazolyl, tetrazolyl, pyrazolyl, pyridinyl, quinolinyl, isoquinolinyl, acridinyl, pyrazinyl, pyridazinyl, pyrimidinyl, benzimidazolyl, benzothiophenyl or benzofuranyl); amino (primary, secondary or tertiary); o-lower alkyl; o-aryl; aryl; aryl-lower alkyl; -CO 2 CH 3 ;―CONH 2 ;-OCH 2 CONH 2 ;-NH 2 ;-SO 2 NH 2 ;―OCHF 2 ;―CF 3 ;-OCF 3 ;-NH(alkyl);-N(alkyl) 2 ;-N(aryl);-N(alkyl)(aryl);-N(aryl) 2 ;―CHO;―CO(alkyl);―CO(aryl);―CO2 (alkyl); and -CO 2 (aryl), and such moieties also include fused ring structures or bridges, e.g., —OCH 2 These substituents can be optionally substituted with further substituents. All chemical groups disclosed herein can be optionally substituted unless otherwise specified.

[0037] The term "linear" refers to an organic compound or moiety that does not contain side chains or cyclic structures. That is, the carbon atoms of the organic compound or moiety all form a single linear arrangement. A linear compound or moiety may be substituted or unsubstituted, as well as saturated or unsaturated.

[0038] The term “halogen” or “halo” refers to F, Cl, Br or I.

[0039] The term "monomer unit" refers to a building block that a single monomer contributes to the structure of a polymer.

[0040] The term "structural unit" refers to all monomer units contributed by the same type of monomer in a polymer.

[0041] The term "carboxylate" refers to a functional group derived from a carboxylic acid in which the proton of the carboxylic acid is replaced with a cation. In some embodiments, the proton of the carboxylic acid is replaced with a metal cation. In some embodiments, the proton of the carboxylic acid is replaced with an ammonium ion.

[0042] The term "homogenizer" refers to a device that can be used to homogenize materials. The term "homogenization" refers to the process of distributing materials evenly throughout a fluid. Non-limiting examples of homogenizers include turbulator mixers, planetary mixers, blenders, and ultrasonic generators.

[0043] The term "mill" refers to a device that reduces the particle size of materials, including mixers that can be used to mix or stir different materials to produce a homogenous mixture. Mixing can be accomplished by using a variety of means, including but not limited to the surface of a container, pressurized gas, or heavy spheres.

[0044] The term "applying" refers to the act of laying or spreading a substance on a surface.

[0045] The term "current collector" refers to any conductive substrate that can contact the electrode layer and conduct the current flowing to the electrode during discharge or charging of the secondary battery. Non-limiting examples of current collectors include a single conductive metal layer or substrate, and a single conductive metal layer or substrate covered with a conductive coating layer, such as a carbon black-based coating layer. The conductive metal layer or substrate may be in the form of a foil or a porous body with a three-dimensional network structure, and may be a polymeric material or a metallic material or a metallized polymer. In some embodiments, the three-dimensional porous current collector is covered with a conformal carbon layer.

[0046] The term "electrode layer" refers to a layer in contact with the current collector that contains an electrochemically active material. In some embodiments, the electrode layer is made by applying a coating to the current collector. In some embodiments, the electrode layer is disposed on one or both sides of the current collector. In other embodiments, a three-dimensional porous current collector is conformally coated onto the electrode layer.

[0047] The term "room temperature" refers to a room temperature of about 18° C. to about 30° C., e.g., 18° C., 19° C., 20° C., 21° C., 22° C., 23° C., 24° C., 25° C., 26° C., 27° C., 28° C., 29° C., or 30° C. In some embodiments, room temperature refers to a temperature of about 20° C.±1° C. or±2° C. or±3° C. In other embodiments, room temperature refers to a temperature of about 22° C. or about 25° C.

[0048] The term "solids" refers to the amount of non-volatile material remaining after evaporation.

[0049] "Peel strength" refers to the amount of force required to separate a current collector and an electrode active material coating that are adhered to each other. It is a measure of the bond strength between these two materials and is usually expressed in N / cm.

[0050] The term "adhesive strength" refers to the amount of force required to separate a current collector and a polymeric material coating that are adhered to each other. It is a measure of the strength of the bond between two such materials, usually expressed in N / cm.

[0051] The term "Ampere-hour (Ah)" refers to the unit used to specify the storage capacity of a battery. For example, a battery with a capacity of 1Ah can supply 1 amp of current for 1 hour, or 0.5A of current for 2 hours, etc. Thus, 1 Ampere-hour (Ah) is equivalent to 3,600 coulombs of charge. Similarly, the term "milliamp-hour (mAh)" refers to the unit of storage capacity of a battery and is 1,000 / 1 of 1 Ampere-hour.

[0052] In the following description, all numbers disclosed herein are approximate, regardless of whether the word "about" or "approximately" is used in connection therewith. They may vary by 1%, 2%, 5%, or even 10 to 20%. The lower limit R L , and upper limit R U Whenever a numerical range is disclosed, any number falling within that range is specifically disclosed. Specifically disclosed are any number within the range where R=R L +k*(R U -R L ), where k is a variable ranging from 0 percent to 100 percent. Additionally, any numerical range defined by the number of two R's, as defined above, is also specifically disclosed.

[0053] Herein, all references to the singular include a reference to the plural and vice versa. Herein, where the context permits, all references to "aqueous solvent" may refer specifically to water.

[0054] Conductive agents are commonly employed in cathode formulations to enhance the electrical conductivity of the cathode. Carbon-based materials, particularly carbon nanotubes (CNTs), find application as conductive agents due to their attractive mechanical properties, i.e., tensile strength and modulus, remarkable flexibility, excellent thermal and electrical conductivity, low percolation threshold (the weight loading at which a rapid drop in resistivity occurs), and small size and high aspect ratio (ratio of length to diameter). The addition of CNTs to an electrode appreciably improves the electrochemical performance of the electrode.

[0055] However, CNTs do not disperse well in most solvents because the strong intermolecular interactions between CNTs cause them to aggregate into bundles or clumps. Therefore, despite their favorable properties, the difficulty in processing CNTs has hindered their widespread use in battery-related applications. Developing methods to improve the dispersion of CNTs in aqueous solvents such as water is a high priority, especially for their greater safety and environmental compatibility.

[0056] Therefore, we propose a novel conductive composition containing CNTs, a copolymer, and an aqueous solvent. The copolymer has good adhesion to the CNT surface and high affinity to the aqueous solvent. Therefore, the CNTs can be effectively dispersed in the aqueous solvent of the conductive composition, which makes it easy to process. The conductive composition can also maintain excellent CNT performance in various aspects, such as electrical conductivity. Therefore, such a conductive composition is very suitable for use in battery electrode slurries.

[0057] In certain embodiments, the aqueous solvent is water. In some embodiments, the aqueous solvent is tap water, bottled water, purified water, pure water, distilled water, deionized water (DI water), D 2 O, and combinations thereof.

[0058] In some embodiments, the aqueous solvent consists solely of water, ie, the percentage of water in the aqueous solvent is 100% by weight, and there are no trace components present in the aqueous solvent.

[0059] In some embodiments, the CNTs may be selected from the group consisting of multi-walled carbon nanotubes (MWCNTs), few-walled carbon nanotubes (FWCNTs), double-walled carbon nanotubes (DWCNTs), single-walled carbon nanotubes (SWCNTs), and combinations thereof. The CNTs used in the present invention are not preferably in the form of a paste, slurry, or composition containing multiple components, because these pastes, slurries, or compositions often also contain additives to disperse the CNTs. These additives may interfere with the ability of the copolymer to disperse the CNTs in the aqueous solvent of the conductive composition or the electrode slurry produced therefrom. Furthermore, the organic solvent used as the dispersion medium for the CNTs may also affect the ability of the copolymer to disperse the CNTs in the aqueous conductive composition or the electrode slurry produced therefrom. Therefore, it is preferable to use dry CNTs in the present invention, for example in the form of a powder.

[0060] The diameter of CNTs ranges from a few nm to tens of nm, and the length ranges from a few μm to hundreds of μm. As a result, CNTs have a large aspect ratio (ratio of length to diameter). In some embodiments, the average diameter of CNTs is about 0.1 nm to about 100 nm, about 0.1 nm to about 90 nm, about 0.1 nm to about 80 nm, about 0.1 nm to about 70 nm, about 0.1 nm to about 60 nm, about 0.1 nm to about 50 nm, about 0.1 nm to about 40 nm, about 0.1 nm to about 30 nm, about 1 nm to about 100 nm, about 1 nm to about 90 nm, about 1 nm to about 80 nm, about 1 nm to about 70 nm, about 1 nm to about 60 nm, about 1 nm to about 50 nm, about 1 nm to about 40 nm, about 1 nm to about 50 nm, about 1 nm to about 60 nm, about 1 nm to about 70 nm, about 1 nm to about 80 nm, about 1 nm to about 80 nm, about 1 nm to about 90 nm, about 1 nm to about 90 nm, about 1 nm to about 80 nm, about 1 nm to about 70 nm, about 1 nm to about 60 nm, about 1 nm to about 50 nm, about 1 nm to about 40 nm, about 1 nm to about 10 ... to about 30 nm, about 1 nm to about 25 nm, about 1 nm to about 20 nm, about 1 nm to about 15 nm, about 3 nm to about 50 nm, about 3 nm to about 40 nm, about 3 nm to about 30 nm, about 3 nm to about 25 nm, about 3 nm to about 20 nm, about 3 nm to about 15 nm, about 5 nm to about 30 nm, about 5 nm to about 25 nm, about 5 nm to about 20 nm, about 5 nm to about 15 nm, about 5 nm to about 10 nm, about 7 nm to about 25 nm, about 7 nm to about 20 nm, about 7 nm to about 15 nm, or about 7 nm to about 10 nm.

[0061] In some embodiments, the average diameter of the CNTs is less than 100 nm, less than 90 nm, less than 80 nm, less than 70 nm, less than 60 nm, less than 50 nm, less than 40 nm, less than 30 nm, less than 25 nm, less than 20 nm, less than 15 nm, less than 13 nm, less than 11 nm, less than 9 nm, less than 7 nm, less than 5 nm, less than 3 nm, or less than 1 nm. In some embodiments, the average diameter of the CNTs is greater than 0.1 nm, greater than 1 nm, greater than 3 nm, greater than 5 nm, greater than 7 nm, greater than 9 nm, greater than 11 nm, greater than 13 nm, greater than 15 nm, greater than 20 nm, greater than 25 nm, greater than 30 nm, greater than 40 nm, greater than 50 nm, greater than 60 nm, greater than 70 nm, greater than 80 nm, or greater than 90 nm.

[0062] In some embodiments, the average length of the CNTs is from about 0.1 μm to about 500 μm, from about 0.1 μm to about 400 μm, from about 0.1 μm to about 300 μm, from about 0.1 μm to about 250 μm, from about 0.1 μm to about 200 μm, from about 0.1 μm to about 150 μm, from about 0.1 μm to about 100 μm, from about 1 μm to about 500 μm, from about 1 μm to about 400 μm, from about 1 μm to about 300 μm, from about 1 μm to about 250 μm, from about 1 μm to about 200 μm, from about 1 μm to about 150 μm, from about 1 μm to about 100 μm, from about 1 μm to about 8 ...500 μm, from about 1 μm to about 500 μm, from about 1 μm to about 500 μm, from about 1 μm to about 300 μm, from about 1 μm to about 250 μm, from about 1 μm to about 200 μm, from about 1 μm to about 150 μm, from about 1 μm to about 100 μm, from about 1 μm to about 60 μm, about 1 μm to about 50 μm, about 5 μm to about 500 μm, about 5 μm to about 300 μm, about 5 μm to about 200 μm, about 5 μm to about 100 μm, about 5 μm to about 50 μm, about 5 μm to about 40 μm, about 5 μm to about 30 μm, about 5 μm to about 20 μm, about 20 μm to about 200 μm, about 20 μm to about 100 μm, about 20 μm to about 50 μm, about 50 μm to about 250 μm, about 50 μm to about 200 μm, about 50 μm to about 150 μm, about 50 μm to about 100 μm, or about 50 μm to about 80 μm.

[0063] In certain embodiments, the average length of the CNTs is less than 500 μm, less than 400 μm, less than 300 μm, less than 250 μm, less than 200 μm, less than 150 μm, less than 100 μm, less than 80 μm, less than 60 μm, less than 50 μm, less than 40 μm, less than 30 μm, less than 20 μm, less than 15 μm, less than 10 μm, less than 5 μm, or less than 1 μm. In some embodiments, the average length of the CNTs is greater than 0.1 μm, greater than 1 μm, greater than 5 μm, greater than 10 μm, greater than 15 μm, greater than 20 μm, greater than 30 μm, greater than 40 μm, greater than 50 μm, greater than 60 μm, greater than 80 μm, greater than 100 μm, greater than 150 μm, greater than 200 μm, greater than 250 μm, greater than 300 μm, or greater than 400 μm.

[0064] In some embodiments, the aspect ratio of the CNTs is from about 10 to about 5×10 6 , from about 50 to about 5 × 10 6 , from about 100 to about 5 × 106 , from about 200 to about 5 × 10 6 , from about 400 to about 5 × 10 6 , from about 600 to about 5 × 10 6 , from about 800 to about 5 × 10 6 , about 1×10 3 From about 5 × 10 6 , about 5×10 3 From about 5 × 10 6 , about 1×10 4 From about 5 × 10 6 , about 5×10 4 From about 5 × 10 6 , about 1×10 5 From about 5 × 10 6 , from about 10 to about 1 x 10 6 , from about 50 to about 1 × 10 6 , from about 100 to about 1×10 6 , from about 200 to about 1×10 6 , from about 400 to about 1 × 10 6 , from about 600 to about 1 × 10 6 , from about 800 to about 1 × 10 6 , about 1×10 3 From about 1×10 6 , about 5×10 3 From about 1×10 6 , about 1×10 4 From about 1×10 6 , about 5×10 4 From about 1×10 6 , about 1×10 5 From about 1×10 6 , from about 100 to about 3 × 10 5 , from about 200 to about 3 × 10 5 , from about 400 to about 3 × 10 5 , from about 600 to about 3 × 10 5 , from about 800 to about 3 × 10 5 , about 1×10 3 From about 3 × 10 5 , about 5×10 3 From about 3 × 10 5 , about 1×10 4 From about 3 × 10 5 , from about 100 to about 1×10 5 , from about 500 to about 1 × 10 5 , about 1×10 3 From about 1×105 , about 5×10 3 From about 1×10 5 , about 1×10 4 From about 1×10 5 , about 2×10 4 From about 1×10 5 , about 4×10 4 From about 1×10 5 , from about 500 to about 4 × 10 4 , about 1×10 3 From about 4 × 10 4 , about 5×10 3 From about 4 × 10 4 , about 1×10 4 From about 4 × 10 4 , about 1×10 3 From about 1×10 4 , about 5×10 3 From about 1×10 4 , about 1×10 3 From about 6 × 10 3 , about 2×10 3 From about 6 × 10 3 , or about 4 × 10 3 From about 6 × 10 3 It is.

[0065] In one embodiment, the aspect ratio of the CNTs is 5×10 6 Less than 1×10 6 Less than 3×10 5 Less than 1×10 5 Less than 8×10 4 Less than 6×10 4 Less than 4×10 4 Less than 2×10 4 Less than 1×10 4 Less than 8×10 3 Less than 6×10 3 Less than 4×10 3 Less than 2×10 3 Less than 1×10 3 In some embodiments, the aspect ratio of the CNTs is greater than 10, greater than 50, greater than 100, greater than 200, greater than 400, greater than 600, greater than 800, less than 1×103 Greater than or equal to 2 x 10 3 Greater than or equal to 4 x 10 3 Greater than 6×10 3 Greater than or equal to 8 x 10 3 Greater than or equal to 1×10 4 Greater than or equal to 2 x 10 4 Greater than or equal to 4 x 10 4 Greater than 6×10 4 Greater than or equal to 8 x 10 4 Greater than or equal to 1×10 5 Greater than or equal to 3 x 10 5 Greater than or equal to 1×10 6 Greater than.

[0066] Due to their small size, CNTs have a high specific surface area. In some embodiments, the BET specific surface area of ​​CNTs is about 100 m 2 / g to about 1,500m 2 / g, about 100m 2 / g to about 1,250m 2 / g, about 100m 2 / g to about 1,000m 2 / g, about 100m 2 / g to about 800m 2 / g, about 100m 2 / g to about 700m 2 / g, about 100m 2 / g to about 600m 2 / g, about 100m 2 / g to about 500m 2 / g, about 100m 2 / g to about 450m 2 / g, about 100m 2 / g to about 400m 2 / g, about 100m 2 / g to about 350m 2 / g, about 100m 2 / g to about 300m 2 / g, about 100m 2 / g to about 250m 2 / g, approximately 100m 2 / g to about 225m 2 / g, about 100m 2 / g to about 200m2 / g, approx. 150m 2 / g to about 1,000m 2 / g, approx. 150m 2 / g to about 800m 2 / g, approx. 150m 2 / g to about 700m 2 / g, approx. 150m 2 / g to about 600m 2 / g, approx. 150m 2 / g to about 500m 2 / g, approx. 150m 2 / g to about 400m 2 / g, approx. 150m 2 / g to about 300m 2 / g, approx. 200m 2 / g to about 700m 2 / g, approx. 200m 2 / g to about 600m 2 / g, approx. 200m 2 / g to about 500m 2 / g, approx. 200m 2 / g to about 400m 2 / g, approx. 200m 2 / g to about 300m 2 / g, approx. 250m 2 / g to about 500m 2 / g, approx. 250m 2 / g to about 400m 2 / g, or about 250m 2 / g to about 350m 2 / g.

[0067] In one embodiment, the BET specific surface area of ​​the CNTs is 1,500 m 2 / g or less, 1,250m 2 / g, less than 1,000m 2 / g, less than 800m 2 / g, 700m 2 / g, less than 600m 2 / g, less than 500m 2 / g, 450m 2 / g, 400m 2 / g, less than 350m 2 / g, less than 300m 2 / g, 250m 2 / g, 225m 2 / g, less than 200m 2 / g, less than 175m 2 / g, 150m 2 / g, 140m 2 / g, less than 130m 2 / g, 120m 2 / g or less than 110m 2 In some embodiments, the BET specific surface area of ​​the CNTs is less than 100 m 2 / g or greater than 110m 2 / g or greater than 120m 2 / g or greater than 130m 2 / g or greater than 140m 2 / g or greater than 150m 2 / g or greater than 175m 2 / g or greater than 200m 2 / g or greater than 225m 2 / g or greater than 250m 2 / g or greater than 300m 2 / g or greater than 350m 2 / g or greater than 400m 2 / g or greater than 450m 2 / g or greater than 500m 2 / g or greater than 600m 2 / g or greater than 700m 2 / g or greater than 800m 2 / g or greater than 1,000m 2 / g or greater than 1,250m 2 / g or greater.

[0068] The copolymer formulation allows the CNTs to have excellent adhesion to the copolymer while at the same time allowing the copolymer to be easily solvated by an aqueous solvent. As a result, the copolymer can enhance the dispersion of the CNTs in the aqueous solvent of the conductive composition and any electrode slurry produced therefrom. In one embodiment, the copolymer comprises three structural units (a), (b) and (c). The structural unit (a) comprises one or more cyano group-containing monomer units, the structural unit (b) comprises one or more carboxylate salt group-containing monomer units, and the structural unit (c) comprises one or more amide group-containing monomer units. When the copolymer has the structural units (a), (b) and (c) in the ratios disclosed below, the copolymer has excellent properties for enhancing CNT dispersion.

[0069] The cyano group of the structural unit (a) can strongly interact with CNTs, which allows the CNTs to be reliably attached to the copolymer, and in combination with the action of other structural units of the copolymer, improves the dispersion of the CNTs in the aqueous solvent of the conductive composition.

[0070] In some embodiments, one or more monomer units of the structural unit (a) are derived from a cyano group-containing monomer. The cyano group-containing monomer includes an α,β-ethylenically unsaturated nitrile monomer. In some embodiments, the cyano group-containing monomer is acrylonitrile, α-halogenoacrylonitrile, α-alkylacrylonitrile, or a combination thereof. In some embodiments, the cyano group-containing monomer is α-chloroacrylonitrile, α-bromoacrylonitrile, α-fluoroacrylonitrile, methacrylonitrile, α-ethylacrylonitrile, α-isopropylacrylonitrile, α-n-hexylacrylonitrile, α-methoxyacrylonitrile, 3-methoxyacrylonitrile, 3-ethoxyacrylonitrile, α-acetoxyacrylonitrile, α-phenylacrylonitrile, α-tolylacrylonitrile, α-(methoxyphenyl)acrylonitrile, α-(chlorophenyl)acrylonitrile, α-(cyanophenyl)acrylonitrile, vinylidene cyanide, or a combination thereof.

[0071] The proportion of structural unit (a) in the copolymer is important. If the proportion of structural unit (a) is too low, it is believed that the adhesion of the CNTs to the copolymer will be poor. Conversely, if the proportion of structural unit (a) is too high, it may result in insufficient solvation. In either case, the dispersion of the CNTs through the action of the copolymer will be insufficient. In some embodiments, the proportion of structural unit (a) in the copolymer is, in mole %, based on the total moles of monomer units present in the copolymer, from about 20% to about 70%, from about 20% to about 65%, from about 20% to about 60%, from about 20% to about 55%, from about 20% to about 50%, from about 20% to about 45%, from about 20% to about 40%, from about 30% to about 70%, from about 40% to about 70%, from about 40% to about 68%, from about 40% to about 65%, from about 40% to about 62%, from about 40% to about 60%, from about 40% to about 58%, from about 40% to about 55%, from about 40% to about 52%, from about 40% to about 50%, from about 40% to about 48%, from about 40% to about 45%, from about 45% to about 70%, about 45% to about 68%, about 45% to about 65%, about 45% to about 62%, about 45% to about 60%, about 45% to about 58%, about 45% to about 55%, about 45% to about 52%, about 45% to about 50%, about 50% to about 70%, about 50% to about 68%, about 50% to about 65%, about 50% to about 62% %, about 50% to about 60%, about 50% to about 58%, about 50% to about 55%, about 55% to about 70%, about 55% to about 68%, about 55% to about 65%, about 55% to about 62%, about 55% to about 60%, about 60% to about 70%, about 60% to about 68%, about 60% to about 65%, or about 65% to about 70%.

[0072] In some embodiments, the proportion of structural units (a) in the copolymer, in mole percent, based on the total moles of monomer units present in the copolymer, is less than 70%, less than 68%, less than 65%, less than 62%, less than 60%, less than 58%, less than 55%, less than 52%, less than 50%, less than 48%, less than 45%, less than 42%, less than 40%, less than 38%, less than 35%, less than 32%, less than 30%, less than 28%, less than 25%, or less than 22%. In some embodiments, the proportion of structural units (a) in the copolymer, in mole percent, based on the total moles of monomeric units present in the copolymer, is greater than 20%, greater than 22%, greater than 25%, greater than 28%, greater than 30%, greater than 32%, greater than 35%, greater than 38%, greater than 40%, greater than 42%, greater than 45%, greater than 48%, greater than 50%, greater than 52%, greater than 55%, greater than 58%, greater than 60%, greater than 62%, greater than 65%, or greater than 68%.

[0073] Carboxylate groups are salts of carboxylic acid groups. In an aqueous solvent such as water, the carboxylate groups dissociate into anionic carboxylate groups and cations. The carboxylate groups, being charged species, easily attract polar molecules of the aqueous solvent to form a solvation shell (hydration shell in the case of water). Thus, the presence of the carboxylate groups of structural unit (b) in the copolymer results in solvation of the copolymer. Thus, the copolymer can increase the dispersion of CNTs in the aqueous solvent of the conductive composition because the CNTs are first attached to the copolymer via structural unit (a) to form a CNT-copolymer complex, and thus the solvation of the CNT-copolymer complex by the molecules of the aqueous solvent of the conductive composition.

[0074] It is not preferred to substitute one or more carboxylate-containing monomer units in the copolymer of the present invention with one or more carboxylate-containing monomer units. Although both have very similar structures, copolymers containing carboxylate-containing monomer units have been found to be less effective at improving CNT dispersion compared to similar copolymers containing carboxylate-containing monomer units. This is likely because both carboxylate and carboxylate groups undergo solvation, but while dissociation of the carboxylate groups is complete, dissociation of the carboxylate groups hardly occurs. The presence of undissociated carboxylic acids results in weaker solvation of the carboxylate groups, since solvation through ionic interactions, which can only occur in dissociated species, is much stronger than polar and hydrogen bonding interactions. It is therefore important to maximize the presence of carboxylate-containing monomer units in the copolymer, rather than carboxylate-containing monomer units.

[0075] In some embodiments, one or more of the monomer units of the structural unit (b) comprises an alkali metal cation. Examples of alkali metals that form the alkali metal cation include lithium, sodium, and potassium. In some embodiments, one or more of the monomer units of the structural unit (b) comprises an ammonium cation.

[0076] In some embodiments, one or more of the monomer units of structural unit (b) is derived from a carboxylate group-containing monomer, hi some embodiments, the carboxylate group-containing monomer is an acrylate salt, a methacrylate salt, a crotonate salt, a 2-butyl crotonate salt, a cinnamate salt, a maleate salt, a maleic anhydride salt, a fumarate salt, an itaconate salt, an itaconate anhydride salt, a tetraconate salt, or a combination thereof. In certain embodiments, the carboxylate group-containing monomer is a 2-ethyl acrylate salt, an isocrotonic acid salt, a cis-2-pentenoic acid salt, a trans-2-pentenoic acid salt, an angelic acid salt, a tiglic acid salt, a 3,3-dimethyl acrylate salt, a 3-propyl acrylate salt, a trans-2-methyl-3-ethyl acrylate salt, a cis-2-methyl-3-ethyl acrylate salt, a 3-isopropyl acrylate salt, a trans-3-methyl-3-ethyl acrylate salt, a cis-3-methyl-3-ethyl acrylate salt, a 2-isopropyl acrylate salt, a trimethyl acrylate salt, a 2-methyl-3,3-diethyl acrylate salt, a 3-butyl acrylate salt, a 2-butyl acrylate salt, a 2-pentyl acrylate salt, a 2-methyl-2-hexenoic acid salt, a trans-3-methyl-2-hexenoic acid salt, a 3-methyl-3-propyl acrylate salt, a 2-ethyl-3-propyl acrylate salt, a acrylate salt, 2,3-diethyl acrylate salt, 3,3-diethyl acrylate salt, 3-methyl-3-hexyl acrylate salt, 3-methyl-3-tert-butyl acrylate salt, 2-methyl-3-pentyl acrylate salt, 3-methyl-3-pentyl acrylate salt, 4-methyl-2-hexenoate salt, 4-ethyl-2-hexenoate salt, 3-methyl-2-ethyl-2-hexenoate salt, 3-tert-butyl acrylate salt, 2,3-di Methyl-3-ethyl acrylate salt, 3,3-dimethyl-2-ethyl acrylate salt, 3-methyl-3-isopropyl acrylate salt, 2-methyl-3-isopropyl acrylate salt, trans-2-octenoate salt, cis-2-octenoate salt, trans-2-decenoate salt, α-acetoxy acrylate salt, β-trans-arylxyacrylate salt, α-chloro-β-E-methoxy acrylate salt, or a combination thereof.In some embodiments, the carboxylate group-containing monomer is a methyl maleate salt, a dimethyl maleate salt, a phenyl maleate salt, a bromo maleate salt, a chloromaleate salt, a dichloromaleate salt, a fluoromaleate salt, a difluoro maleate salt, or a combination thereof.

[0077] The proportion of structural unit (b) in the copolymer is very important. If the proportion of structural unit (b) is too low, the copolymer is less solvated and the dispersion of CNTs through the CNT-copolymer composite is poor. Conversely, if the proportion of structural unit (b) is too high, the adhesion of CNTs to the copolymer is poor, and the dispersion of CNTs through the CNT-copolymer composite is poor because the copolymer then adopts a rod-like conformation, which weakens the steric repulsion between the CNT-copolymer composite. Therefore, the dispersion of CNTs is also poor. In some embodiments, the proportion of structural unit (b) in the copolymer is, in mole percent, based on the total moles of monomer units present in the copolymer, from about 10% to about 50%, from about 15% to about 50%, from about 20% to about 50%, from about 25% to about 50%, from about 30% to about 50%, from about 32% to about 50%, from about 35% to about 50%, from about 38% to about 50%, from about 40% to about 50%, from about 20% to about 50%, from about 35% to about 50%, from about 38% to about 50%, from about 40 ... about 40%, about 22% to about 40%, about 25% to about 40%, about 28% to about 40%, about 30% to about 40%, about 32% to about 40%, about 35% to about 40%, about 20% to about 35%, about 22% to about 35%, about 25% to about 35%, about 28% to about 35%, about 30% to about 35%, about 20% to about 30%, about 22% to about 30%, about 20% to about 25%, or about 22% to about 25%.

[0078] In some embodiments, the proportion of structural units (b) in the copolymer, in mole percent, based on the total moles of monomer units present in the copolymer, is less than 50%, less than 48%, less than 45%, less than 42%, less than 40%, less than 38%, less than 35%, less than 32%, less than 30%, less than 28%, less than 25%, less than 22%, less than 20%, less than 18%, less than 15%, or less than 12%. In some embodiments, the proportion of structural units (b) in the copolymer, in mole percent based on the total moles of monomeric units present in the copolymer, is greater than 10%, greater than 12%, greater than 15%, greater than 18%, greater than 20%, greater than 22%, greater than 25%, greater than 28%, greater than 30%, greater than 32%, greater than 35%, greater than 38%, greater than 40%, greater than 42%, greater than 45%, or greater than 48%.

[0079] It was also found that the mere presence of structural units (a) and (b) still resulted in copolymers that were unable to disperse CNTs in the aqueous solvent of the conductive composition, and that when copolymers containing structural units (a) and (b) were used, CNT aggregation was still observed. Unexpectedly, when the copolymer structure contained structural unit (c) containing one or more amide group-containing monomer units, the copolymer was very effective in dispersing CNTs in the aqueous solvent of the conductive composition. A possible explanation for this is that the presence of structural unit (c) in the copolymer may cause the copolymer to adopt a more spherical conformation instead of a more rod-like conformation. As a result, the steric repulsion between the CNT-copolymer complex increases, and thus the CNT dispersion improves. In addition, the amide group has the property of hydrogen bonding interactions with aqueous solvent molecules, which means that one or more amide groups in structural unit (c) can also contribute to the solvation of the copolymer, thereby improving the dispersion of the CNTs. Therefore, the presence of structural unit (c) in the copolymer is important.

[0080] In some embodiments, one or more monomer units of the structural unit (c) are derived from an amide group-containing monomer. In some embodiments, the amide group-containing monomer is selected from the group consisting of acrylamide, methacrylamide, N-methyl methacrylamide, N-ethyl methacrylamide, N-n-propyl methacrylamide, N-isopropyl methacrylamide, isopropyl acrylamide, N-n-butyl methacrylamide, N-isobutyl methacrylamide, N,N-dimethyl acrylamide, N,N-dimethyl methacrylamide, N,N-diethyl acrylamide, N,N-diethyl methacrylamide, N-methylol methacrylamide, N-(methoxymethyl) methacrylamide, N-(ethoxymethyl) methacrylamide, N-(propoxymethyl)methacrylamide, N-(butoxymethyl)methacrylamide, N,N-dimethylmethacrylamide, N,N-dimethylaminopropylmethacrylamide, N,N-dimethylaminoethylmethacrylamide, N,N-dimethylolmethacrylamide, diacetone methacrylamide, diacetone acrylamide, methacryloylmorpholine, N-hydroxylmethacrylamide, N-methoxymethylacrylamide, N-methoxymethylmethacrylamide, N,N'-methylenebisacrylamide (MBA), N-hydroxymethylacrylamide, or combinations thereof.

[0081] The proportion of structural unit (c) in the copolymer is important. If the proportion of structural unit (c) is too low, the copolymer will have a low ability to disperse CNTs, as described above. Conversely, if the proportion of structural unit (c) is too high, it means that the proportion of structural units (a) and / or (b) is relatively low, resulting in weak intermolecular interactions between the copolymer and the CNTs and poor solvation of the CNT-copolymer composite. In some embodiments, the proportion of structural unit (c) in the copolymer is about 6% to about 25%, about 7% to about 25%, about 8% to about 25%, about 9% to about 25%, about 10% to about 25%, about 11% to about 25%, about 12% to about 25%, about 13% to about 25%, about 14% to about 25%, about 15% to about 25%, about 16% to about 25%, about 17% to about 25%, about 20% to about 25%, about 21% to about 25%, about 22% to about 25%, about 23% to about 25%, about 24% to about 25%, about 25% to about 25%, about 26% to about 25%, about 27% to about 25%, about 28% to about 25%, about 29% to about 30%, about 31% to about 31%, about 32% to about 32%, about 33% to about 33%, about 34% to about 34%, about 35% to about 35%, about 36% to about 35%, about 37% to about 35%, about 38% to about 35%, about 39% to about 40%, about 40% to about 40%, about 41% to about 40%, about 42% to about 40%, about 43% to about 40%, % to about 25%, about 18% to about 25%, about 19% to about 25%, about 20% to about 25%, about 10% to about 22%, about 10% to about 20%, about 11% to about 20%, about 12% to about 20%, about 13% to about 20%, about 14% to about 20%, about 15% to about 20%, about 10% to about 18%, about 11% to about 18%, about 12% to about 18%, about 13% to about 18%, about 10% to about 15%, or about 11% to about 15%.

[0082] In some embodiments, the proportion of structural units (c) in the copolymer, in mole percent, based on the total moles of monomer units present in the copolymer, is less than 25%, less than 24%, less than 23%, less than 22%, less than 21%, less than 20%, less than 19%, less than 18%, less than 17%, less than 16%, less than 15%, less than 14%, less than 13%, less than 12%, less than 11%, less than 10%, less than 9%, less than 8%, or less than 7%. In some embodiments, the proportion of structural units (c) in the copolymer, in mole percent based on the total moles of monomeric units present in the copolymer, is greater than 6%, greater than 7%, greater than 8%, greater than 9%, greater than 10%, greater than 11%, greater than 12%, greater than 13%, greater than 14%, greater than 15%, greater than 16%, greater than 17%, greater than 18%, greater than 19%, greater than 20%, greater than 21%, greater than 22%, greater than 23%, or greater than 24%.

[0083] There are no particular limitations on the method of forming the copolymer, except that the performance of the copolymer must be sufficient to improve the dispersion of CNTs in the aqueous solvent of the conductive composition. In some embodiments, the copolymer is formed by polymerization of monomers that meet the requirements of structural units (a), (b), and (c), respectively. In some embodiments, one or more carboxylic acid group-containing monomers are first polymerized with the monomers from which structural units (a) and (c) are derived, and then a base is added to neutralize the carboxylic acid groups to form one or more carboxylate-containing monomer units of structural units (b). In such embodiments, it is preferable to use an excess of base to ensure that all carboxylic acid groups present are neutralized to carboxylate groups.

[0084] The weight average molecular weight of the copolymer (M w) is important. If the weight average molecular weight of the copolymer is too low, the adhesion of the CNTs to the copolymer may be poor, and the ability of the copolymer to provide dispersion of the CNTs may be reduced. Conversely, if the weight average molecular weight of the copolymer is too high, entanglement of the copolymer chains may occur, and dispersion of the CNTs may be poor. In some embodiments, the weight average molecular weight of the copolymer is about 50,000 g / mol to about 200,000 g / mol, about 60,000 g / mol to about 200,000 g / mol, about 70,000 g / mol to about 200,000 g / mol, about 80,000 g / mol to about 200,000 g / mol, about 90,000 g / mol to about 200,000 g / mol, about 90,000 g / mol to about 190,000 g / mol, about 90, 000 g / mol to about 180,000 g / mol, about 90,000 g / mol to about 170,000 g / mol, about 90,000 g / mol to about 160,000 g / mol, about 95,000 g / mol to about 160,000 g / mol, about 100,000 g / mol to about 160,000 g / mol, about 100,000 g / mol to about 150,000 g / mol, or about 100,000 g / mol to about 140,000 g / mol.

[0085] In some embodiments, the weight average molecular weight of the copolymer is less than 200,000 g / mol, less than 190,000 g / mol, less than 180,000 g / mol, less than 170,000 g / mol, less than 160,000 g / mol, less than 150,000 g / mol, less than 140,000 g / mol, less than 130,000 g / mol, less than 120,000 g / mol, less than 110,000 g / mol, less than 100,000 g / mol, less than 90,000 g / mol, less than 80,000 g / mol, less than 70,000 g / mol, or less than 60,000 g / mol. In some embodiments, the weight average molecular weight of the copolymer is greater than 50,000 g / mol, greater than 60,000 g / mol, greater than 70,000 g / mol, greater than 80,000 g / mol, greater than 90,000 g / mol, greater than 100,000 g / mol or greater, greater than 110,000 g / mol, greater than 120,000 g / mol, greater than 130,000 g / mol, greater than 140,000 g / mol, greater than 150,000 g / mol, greater than 160,000 g / mol, greater than 170,000 g / mol, greater than 180,000 g / mol, or greater than 190,000 g / mol.

[0086] The proportion of CNTs in the conductive composition is very important. If such proportion is too low, the effect of CNTs in improving the performance of the battery may not be sufficient. Conversely, if such proportion is too high, the amount of copolymer required to disperse the CNTs increases accordingly, which may affect the performance of the battery due to the addition of an excessive amount of binder. In some embodiments, the percentage of CNTs in the conductive composition is, in weight percent based on the total weight of the conductive composition, about 0.2% to about 3.5%, about 0.2% to about 3%, about 0.2% to about 2.5%, about 0.2% to about 2%, about 0.2% to about 1.5%, about 0.2% to about 1%, about 0.2% to about 0.8%, about 0.2% to about 0.5%, about 0.3% to about 3.5%, about 0.3% to about 3%, about 0.3% to about 2%, about 0.3% to about 1%, about 0.4% to about 3.5%, about 0.4% to about 3%, about 0.4% to about 2%, about 0.4% to about 1%, about 0.5% to about 3.5%, about 0.5% to about 3%, about 0.5% to about 2%, about 0.5% to about 1%, about 0.6% to about 3.5%, about 0.6% to about 3%, about 0.6% to about 2%, about 0.7% to about 3.5%, about 0.7% to about 3%, about 0.7% to about 2%, about 0.8% to about 3.5%, about 0.8% to about 3%, about 0.8% to about 2%, about 0.9% to about 3.5%, about 0.9% to about 2%, about 1% to about 3.5%, about 1% to about 2%, about 1% to about 1.5%, about 1.5% to about 3.5%, about 2% to about 3.5%, or about 2.5% to about 3.5%.

[0087] In some embodiments, the percentage of CNTs in the conductive composition is, by weight, less than 3.5%, less than 3%, less than 2.5%, less than 2%, less than 1.75%, less than 1.5%, less than 1.3%, less than 1.1%, less than 1%, less than 0.9%, less than 0.8%, less than 0.7%, less than 0.6%, less than 0.5%, less than 0.4%, or less than 0.3%, based on the total weight of the conductive composition. In some embodiments, the percentage of CNTs in the conductive composition is, in weight percent, based on the total weight of the conductive composition, greater than 0.2%, greater than 0.3%, greater than 0.4%, greater than 0.5%, greater than 0.6%, greater than 0.7%, greater than 0.8%, greater than 0.9%, greater than 1%, greater than 1.1%, greater than 1.3%, greater than 1.5%, greater than 1.75%, greater than 2%, greater than 2.5%, or greater than 3%.

[0088] The proportion of copolymer in the conductive composition is important: if this proportion is too low, the CNTs may not disperse well in the aqueous solvent of the conductive composition; conversely, if this proportion is too high, the conductive composition may become too viscous, which may affect the processability of the conductive composition. In some embodiments, the percentage of the copolymer in the conductive composition is, in weight percent, based on the total weight of the conductive composition, from about 4% to about 10%, from about 4.5% to about 10%, from about 5% to about 10%, from about 5.5% to about 10%, from about 6% to about 10%, from about 6.5% to about 10%, from about 7% to about 10%, from about 7.5% to about 10%, from about 8% to about 10%, from about 4% to about 8%, from about 4.5% to about 8%, from about 5% to about 8%, from about 5.5% to about 8%, from about 6% to about 8%, from about 4% to about 7%, from about 4.5% to about 7%, from about 5% to about 7%, from about 5.5% to about 7%, from about 6% to about 7%, from about 4% to about 6%, from about 4.5% to about 6%, from about 5% to about 6%, from about 5.5% to about 6%, or from about 4% to about 5%.

[0089] In some embodiments, the percentage of the copolymer in the conductive composition is less than 10%, less than 9%, less than 8%, less than 7.5%, less than 7%, less than 6.8%, less than 6.5%, less than 6.2%, less than 6%, less than 5.8%, less than 5.5%, less than 5.2%, less than 5%, less than 4.8%, less than 4.5%, or less than 4.2% by weight based on the total weight of the conductive composition. In some embodiments, the percentage of the copolymer in the conductive composition is greater than 4%, greater than 4.2%, greater than 4.5%, greater than 4.8%, greater than 5%, greater than 5.2%, greater than 5.5%, greater than 5.8%, greater than 6%, greater than 6.2%, greater than 6.5%, greater than 6.8%, greater than 7%, greater than 7.5%, greater than 8%, or greater than 9% by weight based on the total weight of the conductive composition.

[0090] The ratio of the weight of CNT to the weight of copolymer is particularly important. If the ratio of the weight of CNT to the weight of copolymer is too low, this means that there are too few CNTs relative to the copolymer, and the effect of CNTs in improving the performance of the battery may not be large, or the conductive composition may become too viscous, and the processability of the conductive composition may be affected. Conversely, if the ratio of the weight of CNT to the weight of copolymer is too high, this means that there are too many CNTs relative to the copolymer, and the copolymer may not be sufficient to disperse the CNTs in the aqueous solvent of the conductive composition. In some embodiments, the ratio of the weight of CNTs to the weight of copolymer in the conductive composition is from about 1:20 to about 1:3, from about 1:20 to about 1:4, from about 1:20 to about 1:5, from about 1:20 to about 1:6, from about 1:20 to about 1:7, from about 1:20 to about 1:8, from about 1:20 to about 1:9, from about 1:20 to about 1:10, from about 1:20 to about 1:11, from about 1:20 to about 1:12, about 1:20 to about 1:13, about 1:20 to about 1:14, about 1:20 to about 1:15, about 1:15 to about 1:5, about 1:15 to about 1:6, about 1:15 to about 1:7, about 1:15 to about 1:8, about 1:15 to about 1:9, about 1:15 to about 1:10, about 1:12 to about 1:5, about 1:12 to about 1:6, about 1:12 to about 1:7, or about 1:12 to about 1:8.

[0091] In some embodiments, the ratio of the weight of CNTs to the weight of copolymer in the conductive composition is greater than 1:20, greater than 1:19, greater than 1:18, greater than 1:17, greater than 1:16, greater than 1:15, greater than 1:14, greater than 1:13, greater than 1:12, greater than 1:11, greater than 1:10, greater than 1:9, greater than 1:8, greater than 1:7, greater than 1:6, greater than 1:5, or greater than 1:4. In some embodiments, the ratio of the weight of CNTs to the weight of copolymer in the conductive composition is less than 1:3, less than 1:4, less than 1:5, less than 1:6, less than 1:7, less than 1:8, less than 1:9, less than 1:10, less than 1:11, less than 1:12, less than 1:13, less than 1:14, less than 1:15, less than 1:16, less than 1:17, less than 1:18, or less than 1:19.

[0092] The total percentage of the copolymer and CNT in the conductive composition determines the solids content of the conductive composition. If such percentage is too low, the solids content will be too low, which may result in poor processability of the conductive composition. Conversely, if such percentage is too high, the solids content will be too high, which may similarly affect the processability of the conductive composition. In some embodiments, the total percentage of the copolymer and CNT in the conductive composition is, in weight percent, about 4% to about 13%, about 4.5% to about 13%, about 5% to about 13%, about 5.5% to about 13%, about 6% to about 13%, about 6.5% to about 13%, about 7% to about 13%, about 7.5% to about 13%, about 8% to about 13%, about 8.5% to about 13%, about 9% to about 13%, about 9.5% to about 13%, about 10% to about 13%, about 4% to about 10%, based on the total weight of the conductive composition. , about 4.5% to about 10%, about 5% to about 10%, about 5.5% to about 10%, about 6% to about 10%, about 6.5% to about 10%, about 7% to about 10%, about 4% to about 8%, about 4.5% to about 8%, about 5% to about 8%, about 5.5% to about 8%, about 6% to about 8%, about 4% to about 7%, about 4.5% to about 7%, about 5% to about 7%, about 5.5% to about 7%, about 4% to about 6%, about 4.5% to about 6%, about 5% to about 6%, about 4% to about 5.5%, or about 4% to about 5%.

[0093] In some embodiments, the combined percentage of copolymer and CNTs in the conductive composition is, in weight percent, less than 13%, less than 12%, less than 11%, less than 10%, less than 9.5%, less than 9%, less than 8.5%, less than 8%, less than 7.8%, less than 7.5%, less than 7.2%, less than 7%, less than 9.8%, less than 6.5%, less than 6.2%, less than 6%, less than 5.8%, less than 5.5%, less than 5.2%, less than 5%, less than 4.8%, less than 4.6%, or less than 4.4%, based on the total weight of the conductive composition. In some embodiments, the combined percentage of copolymer and CNTs in the conductive composition is, in weight percent, greater than 4%, greater than 4.2%, greater than 4.4%, greater than 4.6%, greater than 4.8%, greater than 5%, greater than 5.2%, greater than 5.5%, greater than 5.8%, greater than 6%, greater than 6.2%, greater than 6.5%, greater than 6.8%, greater than 7%, greater than 7.2%, greater than 7.5%, greater than 7.8%, greater than 8%, greater than 8.5%, greater than 9%, greater than 9.5%, greater than 10%, greater than 11%, or greater than 12% based on the total weight of the conductive composition.

[0094] The presence of surfactants, coupling agents, or inorganic nanoparticles is not preferred because any of these additives may interfere with the ability of the copolymer to improve the dispersion of the CNTs in the conductive composition. Furthermore, when the conductive composition is used, the presence of such additives may affect the performance of the CNTs or even the application itself.

[0095] In some embodiments, no surfactant is present in the conductive composition. In some embodiments, the conductive composition is free of anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants.

[0096] In some embodiments, anionic surfactants comprising alkyl sulfates, alkyl sulfonates, alkyl carboxylates, alkyl phosphates, alkyl phosphonates, alkyl aromatic sulfates, alkyl aromatic sulfonates, alkyl aromatic carboxylates, alkyl aromatic phosphates, alkyl aromatic phosphonates, alkyl alkoxy sulfates, alkyl alkoxy sulfonates, alkyl alkoxy carboxylates, alkyl alkoxy phosphates, alkyl alkoxy phosphonates, alkyl ester sulfates, alkyl ester sulfonates, alkyl ester carboxylates, alkyl ester phosphates, alkyl ester phosphonates, alkyl ether sulfates, alkyl ether sulfonates, alkyl ether carboxylates, alkyl ether phosphates, alkyl ether phosphonates, or combinations thereof, wherein the counter ion corresponding to each anionic surfactant is independently selected from the group consisting of alkali metal ions, alkaline earth metal ions, ammonium ions, mono- / di- or tri-alkylammonium ions, mono- / di- or tri-(hydroxyalkyl)ammonium ions, and combinations thereof, are not present in the conductive composition.

[0097] In some embodiments, fatty acid salts; polyoxyalkylene alkyl ether acetates; polyoxyalkylene alkyl ether sulfates; higher fatty acid amide sulfonates; N-acylsarcosin salts; polyoxyalkylene alkyl ether phosphates; long chain sulfosuccinates; long chain N-acyl glutamates; polymers and copolymers comprising acrylic acid, anhydrides, esters, vinyl monomers and / or olefins, and their alkali metal, alkaline earth metal and / or ammonium salt derivatives; salts of polycarboxylic acids; formalin condensates of naphthalene sulfonic acid; alkyl naphthalene sulfonic acids; naphthalene sulfonic acids; alkyl naphthalene sulfonates; formalin condensates of naphthalene sulfonates and acids, such as alkali metal salts, alkaline earth metal salts, ammonium salts or amine salts; melamine sulfonic acid; alkyl melamine sulfonic acids; formalin condensates of melamine sulfonic acids; formalin condensates of alkyl melamine sulfonic acids; alkali metal salts, alkaline earth metal salts, ammonium salts and Anionic surfactants, including amine salts; lignosulfonic acid; and alkali metal, alkaline earth metal, ammonium and amine salts of lignosulfonic acid; metal dodecyl sulfates; metal dodecyl sulfonates; metal dodecyl carboxylates; metal dodecyl phosphates; metal dodecyl phosphonates; metal dodecyl ether sulfates; metal dodecyl ether sulfonates; metal dodecyl ether carboxylates; metal dodecyl ether phosphates; metal dodecyl ether phosphonates; metal dodecyl benzene sulfates; metal dodecyl benzene sulfonates; metal dodecyl benzene carboxylates; metal dodecyl benzene phosphates; metal dodecyl benzene phosphonates; metal dodecyl benzene sulfates; metal dodecyl benzene sulfonates; metal dodecyl benzene carboxylates; metal dodecyl benzene phosphates; metal dodecyl benzene phosphonates; metal stearates; olefin sulfonates; alpha olefin sulfonates, or combinations thereof, are not present in the conductive composition.

[0098] In some embodiments, the compound is selected from the group consisting of sodium dodecyl sulfate (SDS), lithium dodecyl sulfate (LDS), sodium lauryl ether sulfate (SLES), lithium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate (SDBS), paraffin sulfonates, ammonium or other alkali or alkaline earth metal sarcosinates, ammonium or other alkali or alkaline earth metal sulfosuccinates, ammonium or other alkali or alkaline earth metal isethionates, ammonium or other alkali or alkaline earth metal taurates, ammonium lauryl sulfate, ammonium laureth sulfate, triethylamine lauryl sulfate, triethylamine laureth sulfate, triethanolamine lauryl sulfate, triethanolamine laureth sulfate, monoethanolamine lauryl sulfate, Monoethanolamine laureth sulfate, diethanolamine lauryl sulfate, diethanolamine laureth sulfate, sodium lauric acid monoglyceride sulfate, sodium lauryl sulfate, sodium laureth sulfate, potassium lauryl sulfate, potassium laureth sulfate, sodium lauryl phosphate, sodium tridecyl phosphate, sodium behenyl phosphate, sodium laureth-2 phosphate, sodium dilauryl phosphate, sodium ditridecyl phosphate, sodium lauroyl sarcosinate, lauroyl sarcosine, cocoyl sarcosine, ammonium cosyl sulfate, sodium cosyl sulfate, sodium trideceth sulfate, sodium tridecyl sulfate, ammonium trideceth sulfate, ammonium tridecyl sulfate, sodium cocoyl isethionate, disodium laureth sulfosuccinate, sodium methyl oleoyl taurate Anionic surfactants, including sodium methyl oleoyl taurate, sodium laureth carboxylate, sodium trideceth carboxylate, sodium lauryl sulfate, potassium cosyl sulfate, potassium lauryl sulfate, monoethanolamine cosyl sulfate, sodium tridecylbenzenesulfonate, ether sulfonates, lithium stearate, sodium stearate, or combinations thereof, are not present in the conductive composition.

[0099] In some embodiments, cationic surfactants, including alkyltrimethylammonium salts such as stearyltrimethylammonium chloride, lauryltrimethylammonium chloride, and cetyltrimethylammonium bromide; dialkyldimethylammonium salts; trialkylmethylammonium salts; tetraalkylammonium salts; alkylamine salts; benzalkonium salts; alkylpyridinium salts; and imidazolium salts, are not present in the conductive composition.

[0100] In some embodiments, non-ionic surfactants including polyoxyalkylene oxide-added alkyl ethers; polyoxyalkylene styrene phenyl ethers; polyhydric alcohols; ester compounds of monovalent fatty acids; polyoxyalkylene alkyl phenyl ethers; polyoxyalkylene fatty acid ethers; polyoxyalkylene sorbitan fatty acid esters; glycerin fatty acid esters; polyoxyalkylene castor oils; polyoxyalkylene hydrogenated castor oils; polyoxyalkylene sorbitol fatty acid esters; polyglycerin fatty acid esters; alkyl glycerin ethers; polyoxyalkylene cholesteryl ethers; alkyl polyglucosides; sucrose fatty acid esters; polyoxyalkylene alkylamines; polyoxyethylene-polyoxypropylene block polymers; sorbitan fatty acid esters; and fatty acid alkanolamides are not present in the conductive composition.

[0101] In some embodiments, amphoteric surfactants including 2-undecyl-N,N-(hydroxyethylcarboxymethyl)-2-imidazoline sodium salt, 2-cocoyl-2-imidazolinium hydroxide-1-carboxyethyloxy disodium salt; imidazoline-based amphoteric surfactants; 2-heptadecyl-N-carboxymethyl-N-hydroxyethylimidazolium betaine, lauryl dimethylaminoacetic acid betaine, alkyl betaines, amido betaines, sulfobetaines and other betaine-based amphoteric surfactants; N-lauryl glycine, N-lauryl β-alanine, N-stearyl β-alanine, lauryl dimethylamino oxide, oleyl dimethylamino oxide, sodium lauroyl glutamate, lauryl dimethylaminoacetic acid betaine, stearyl dimethylaminoacetic acid betaine, cocamidopropyl hydroxysultaine, and 2-alkyl-N-carboxymethyl-N-hydroxyethylimidazolinium betaine are not present in the conductive composition.

[0102] In some embodiments, no coupling agent is present in the conductive composition, hi some embodiments, no silane coupling agent or titanate coupling agent is present in the conductive composition.

[0103] In some embodiments, inorganic nanoparticles are not present in the conductive composition. In some embodiments, inorganic nanoparticles including Cs, Mg, Ca, Sr, Sc, Ti, Zr, Nb, Ta, Cr, Mo, W, Mn, Fe, Ru, Co, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Si, Ge, Sn, Pb, Sb, Te, compounds thereof, or combinations thereof are not present in the conductive composition.

[0104] There are no particular limitations on the method of forming the conductive composition from the copolymer, CNTs, and aqueous solvent, except that all materials should be present in the conductive composition, and that the CNTs and copolymer are well dispersed in the aqueous solvent to form a homogenous mixture, for example by using a homogenizer. However, to ensure that the copolymer can effectively attach to the surface of the CNTs and effectively improve the dispersion of the CNTs in the aqueous solvent, it is preferable to first disperse the copolymer in the aqueous solvent before adding the CNTs to form the conductive composition. The homogenizer used is not particularly limited, except that it must be capable of dispersing the copolymer and CNTs well in the aqueous solvent to form a homogenized conductive composition without damaging the structure of the CNTs. However, ultrasonic generators are not preferred, as it has been found that ultrasound can destroy the structure of the CNTs. Instead, homogenizers that can exert shear forces on the conductive composition during homogenization are preferred, as this ensures a homogenous mixture while minimizing structural damage to the CNTs. Non-limiting examples of suitable homogenizers include agitator mixers, planetary agitator mixers, blenders, mills, etc. There are no particular limitations on the agitation speed, agitation time, or homogenization temperature, except that such conditions must be sufficient for the resulting conductive composition to be homogenous with the CNTs and copolymer well dispersed in the aqueous solvent of the conductive composition.

[0105] In some embodiments, the copolymer is in the form of a copolymer composition that includes the copolymer itself and a solvent, which may be solvent left over from the polymerization process, while in other embodiments, a dry copolymer is used to form the copolymer composition.

[0106] The pH of the conductive composition is important. If the pH of the conductive composition is too low, the carboxylate anions in the copolymer of the conductive composition will accept protons to form the corresponding carboxylic acid groups. As a result, the solvation of the copolymer in the aqueous solvent of the conductive composition will be weak, and the dispersion of CNTs by the copolymer may become poor. In addition, the hydrogen bond interaction between the carboxylic acid groups in the copolymer may cause the copolymer to aggregate and, in turn, the CNTs to aggregate. Conversely, if the pH of the conductive composition is too high, hydrolysis of the cyano groups in the copolymer of the conductive composition may occur. As a result, fewer cyano groups are present in the copolymer, and the intermolecular interaction between the copolymer and the CNTs is weakened. Therefore, the adhesion between the copolymer and the CNTs is also weakened. Therefore, the dispersion of CNTs by the copolymer is less effective. Therefore, it is preferable that the pH of the conductive composition is actually moderately basic.

[0107] In some embodiments, the pH of the conductive composition is from about 7 to about 12, from about 8 to about 12, from about 9 to about 12, from about 10 to about 12, from about 7 to about 11.5, from about 7 to about 11, from about 7 to about 10.5, from about 7 to about 10, from about 7.5 to about 10, from about 8 to about 10, from about 8.5 to about 10, from about 9 to about 10, from about 7 to about 9, from about 7.5 to about 9, from about 8 to about 9, from about 7 to about 8.5, from about 7.5 to about 8.5, from about 8 to about 8.5, from about 7 to about 8, from about 7.5 to about 8, or from about 7 to about 7.5.

[0108] In some embodiments, the pH of the conductive composition is less than 12, less than 11.5, less than 11, less than 10.5, less than 10, less than 9.5, less than 9, less than 8.5, less than 8, or less than 7.5. In some embodiments, the pH of the conductive composition is greater than 7, greater than 7.5, greater than 8, greater than 8.5, greater than 9, greater than 9.5, greater than 10, greater than 10.5, greater than 11, or greater than 11.5.

[0109] The viscosity of the conductive composition is important for the ease of processing of the conductive composition. If the viscosity of the conductive composition is too high, it may be difficult to maintain the homogeneity of the conductive composition and to handle the conductive composition when it is used. Conversely, if the viscosity of the conductive composition is too low, the subsequent processability of the conductive composition may be poor. For example, if a conductive composition with too low a viscosity is used for an electrode slurry, the electrode slurry will have poor stability and poor viscosity characteristics, and it will require a great deal of effort to adjust and control the physical properties of the slurry in order for the slurry to successfully produce an electrode.

[0110] In some embodiments, the dynamic viscosity of the conductive composition at 20° C. is from about 500 mPa·s to about 2,000 mPa·s, from about 600 mPa·s to about 2,000 mPa·s, from about 700 mPa·s to about 2,000 mPa·s, from about 800 mPa·s to about 2,000 mPa·s, from about 900 mPa·s to about 2,000 mPa·s, from about 1,000 mPa·s to about 2,000 mPa·s, from about 1,100 mPa·s to about 2,000 mPa·s, from about 1,200 mPa·s to about 2,000 mPa·s, from about 1,300 mPa·s to about 2,000 mPa·s, or from about 1,400 mPa·s to about 2,000 mPa·s. 0 mPa·s, about 1,500 mPa·s to about 2,000 mPa·s, about 500 mPa·s to about 1,500 mPa·s, about 600 mPa·s to about 1,500 mPa·s, about 700 mPa·s to about 1,500 mPa·s, about 800 mPa·s to about 1,500 mPa·s, about 900 mPa·s to about 1,500 mPa·s, about 1,000 mPa·s to about 1,500 mPa·s, about 500 mPa·s to about 1,000 mPa·s, about 600 mPa·s to about 1,000 mPa·s, about 700 mPa·s to about 1000 mPa·s, or about 500 mPa·s to about 800 mPa·s.

[0111] In some embodiments, the dynamic viscosity of the conductive composition at 20° C. is less than 2,000 mPa·s, less than 1,900 mPa·s, less than 1,800 mPa·s, less than 1,700 mPa·s, less than 1,600 mPa·s, less than 1,500 mPa·s, less than 1,400 mPa·s, less than 1,300 mPa·s, less than 1,200 mPa·s, less than 1,100 mPa·s, less than 1,000 mPa·s, less than 900 mPa·s, less than 800 mPa·s, less than 700 mPa·s, or less than 600 mPa·s. In some embodiments, the dynamic viscosity of the conductive composition at 20° C. is greater than 500 mPa·s, greater than 600 mPa·s, greater than 700 mPa·s, greater than 800 mPa·s, greater than 900 mPa·s, greater than 1,000 mPa·s, greater than 1,100 mPa·s, greater than 1,200 mPa·s, greater than 1,300 mPa·s, greater than 1,400 mPa·s, greater than 1,500 mPa·s, greater than 1,600 mPa·s, greater than 1,700 mPa·s, greater than 1,800 mPa·s, or greater than 1,900 mPa·s.

[0112] 1 shows a sample of the conductive composition of Example 1, which includes the copolymer, CNTs, and water as the aqueous solvent. As shown, the conductive composition is homogeneous without any presence of precipitates or aggregates, indicating that the CNTs are well dispersed in the aqueous solvent of the conductive composition.

[0113] 2a and 2b are images of the dried sample of the conductive composition of Example 1 at 10,000 and 50,000 magnifications, respectively. The copolymer can be seen as a relatively large structure in the background, and the CNTs can be seen as thin white filaments. From the images, it can be seen that the CNTs are attached to the copolymer chains. This indicates that the CNTs are well dispersed in the aqueous solvent of the conductive composition due to the attachment of the CNTs to the copolymer and subsequent solvation of the CNT-copolymer complex. Furthermore, the conductive composition was found to be still stable after a significant period of time, and the conductive composition was found to have excellent CNT performance. Thus, the conductive composition of the present invention facilitates the processing and handling of CNTs without compromising the desirable properties of CNTs.

[0114] The conductive composition of the present invention is highly suitable for use in electrode slurries for batteries. In some embodiments, the battery can be a primary battery or a secondary battery. Some non-limiting examples of battery types include alkaline batteries, aluminum-air batteries, lithium batteries, lithium-air batteries, magnesium batteries, silver oxide batteries, zinc-air batteries, aluminum-ion batteries, lead-acid batteries, lithium-ion batteries, magnesium-ion batteries, potassium-ion batteries, sodium-ion batteries, sodium-air batteries, silicon-air batteries, zinc-ion batteries, and sodium-sulfur batteries. Furthermore, depending on the state of the electrolyte used (i.e., liquid state or solid state), the battery can be classified as a conventional battery (when a liquid electrolyte is used) or a solid-state battery (when a solid electrolyte is used).

[0115] In some embodiments, the electrode slurry comprises an electrode active material and a conductive composition of the present invention. In some embodiments, an additional aqueous solvent is added to the aqueous solvent of the conductive composition in forming the electrode slurry. In some embodiments, the electrode slurry further comprises a binder. In some embodiments, the electrode slurry further comprises a conductive agent. The electrode active material can be a cathode active material or an anode active material. When the electrode slurry comprises a cathode active material, the electrode slurry is a cathode slurry. When the electrode slurry comprises an anode active material, the electrode slurry is an anode slurry.

[0116] In some embodiments, the electrode active material is a cathode active material. In some embodiments, the cathode active material is LiCoO 2 , LiNiO 2 , LiNi 1-x M x O 2 , LiNi x Mn y O 2 , LiCo x Ni y O 2 , Li 1+z Ni x Mn y Co 1-x-y O 2 , LiNi x Co y Al z O 2 , LiV 2 O 5 , LiTiS 2 , LiMoS 2 , LiMnO 2 , LiCrO 2 , LiMn 2 O 4 , Li 2 MnO 3 , LiFeO 2 , LiFePO 4and combinations thereof, wherein each x is independently 0.1 to 0.9; each y is independently 0 to 0.9; each z is independently 0 to 0.4; and M is selected from the group consisting of Co, Mn, Al, Fe, Ti, Ga, Mg, and combinations thereof. In certain embodiments, each x in the above general formula is independently selected from 0.1, 0.125, 0.15, 0.175, 0.2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375, 0.4, 0.425, 0.45, 0.475, 0.5, 0.525, 0.55, 0.575, 0.6, 0.625, 0.65, 0.675, 0.7, 0.725, 0.75, 0.775, 0.8, 0.825, 0.85, 0.875, and 0.9; and each y in the above general formula is independently selected from 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, 0.2 ,0.225,0.25,0.275,0.3,0.325,0.35,0.375,0.4,0.425,0.45,0.475,0.5,0.525,0.55,0.575,0.6,0.625,0.65,0.675,0.7,0.725,0.75,0.775,0.8,0.825 , 0.85, 0.875, and 0.9; each z in the above general formula is independently selected from 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, 0.2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375, and 0.4. In some embodiments, each x, y, and z in the above general formula is independently spaced by 0.01.

[0117] In some embodiments, the cathode active material is LiNi x Mn y O 2 , Li 1+z Ni x Mn y Co 1-x-y O 2 (NMC), LiNi x Co y Al z O 2 (NCA), LiCo x Ni y O 2and combinations thereof, wherein each x is independently 0.4 to 0.6; each y is independently 0.2 to 0.4; and each z is independently 0 to 0.1. In another embodiment, the cathode active material is LiCoO 2 , LiNiO 2 , LiV 2 O 5 , LiTiS 2 , LiMoS 2 , LiMnO 2 , LiCrO 2 , LiMn 2 O 4 , LiFeO 2 or LiFePO 4 In a further embodiment, the cathode active material is not LiNi x Mn y O 2 , Li 1+z Ni x Mn y Co 1-x-y O 2 , LiNi x Co y Al z O 2 or LiCo x Ni y O 2 each x is independently from 0.1 to 0.9; each y is independently from 0 to 0.45; and each z is independently from 0 to 0.2. In certain embodiments, the cathode active material is Li 1+x Ni a Mn b Co c Al (1-a-b-c) O 2 where -0.2≦x≦0.2, 0≦a<1, 0≦b<1, 0≦c<1, and a+b+c≦1. In some embodiments, the cathode active material has the general formula Li 1+x Ni a Mn b Co c Al (1-a-b-c) O 2where 0.33 ≦ a ≦ 0.92, 0.33 ≦ a ≦ 0.9, 0.33 ≦ a ≦ 0.8, 0.4 ≦ a ≦ 0.92, 0.4 ≦ a ≦ 0.9, 0.4 ≦ a ≦ 0.8, 0.5 ≦ a ≦ 0.92, 0.5 ≦ a ≦ 0.9, 0.5 ≦ a ≦ 0.8, 0.6 ≦ a ≦ 0.92, or 0.6 ≦ a ≦ 0.9; 0 ≦ b ≦ 0.5, 0 ≦ b ≦ 0.4, 0 ≦ b ≦ 0.3, 0 ≦ b ≦ 0.2, 0.1 ≦ b ≦ 0.5, 0.1 ≦ b ≦ 0.4, 0.1 ≦ b ≦ 0.3, 0.1 ≦ b ≦ 0.2, 0.2 ≦ b ≦ 0.5, 0.2 ≦ b ≦ 0.4, or 0.2 ≦ b ≦ 0.3; 0 ≦ c ≦ 0.5, 0 ≦ c ≦ 0.4, 0 ≦ c ≦ 0.3, 0.1 ≦ c ≦ 0.5, 0.1 ≦ c ≦ 0.4, 0.1 ≦ c ≦ 0.3, 0.1 ≦ c ≦ 0.2, 0.2 ≦ c ≦ 0.5, 0.2 ≦ c ≦ 0.4, or 0.2 ≦ c ≦ 0.3. In some embodiments, the cathode active material has the general formula LiMPO 4 where M is selected from the group consisting of Fe, Co, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge, or combinations thereof.

[0118] In some embodiments, the cathode active material is LiFePO 4 , LiCoPO 4 , LiNiPO 4 , LiMnPO 4 , LiMnFePO 4 , LiMn x Fe (1-x) PO 4 , and is selected from the group consisting of combinations thereof; where 0 < x < 1. In some embodiments, the cathode active material is LiNi x Mn y O 4 where 0.1 ≦ x ≦ 0.9 and 0 ≦ y ≦ 2. In one embodiment, the cathode active material is xLi 2 MnO 3 ·(1 - x)LiMO 2 where M is selected from the group consisting of Ni, Co, Mn, and combinations thereof; and 0 < x < 1. In some embodiments, the cathode active material is Li 3 V 2 (PO 4 )3 , or LiVPO 4 F. In some embodiments, the cathode active material has the general formula Li 2 MSiO 4 where M is selected from the group consisting of Fe, Co, Mn, Ni, and combinations thereof.

[0119] In certain embodiments, the cathode active material is doped with a dopant selected from the group consisting of Co, Cr, V, Mo, Nb, Pd, F, Na, Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge, and combinations thereof. In some embodiments, the cathode active material is not doped with Co, Cr, V, Mo, Nb, Pd, F, Na, Fe, Ni, Mn, Mg, Zn, Ti, La, Ce, Ru, Si, or Ge. In some embodiments, the cathode active material is not doped with Al, Sn, or Zr.

[0120] In some embodiments, the cathode active material is LiNi 0.33 Mn 0.33 Co 0.33 O 2 (NMC333), LiNi 0.4 Mn 0.4 Co 0.2 O 2 , LiNi 0.5 Mn 0.3 Co 0.2 O 2 (NMC532), LiNi 0.6 Mn 0.2 Co 0.2 O 2 (NMC622), LiNi 0.7 Mn 0.15 Co 0.15 O 2 , LiNi 0.7 Mn 0.1 Co 0.2 O 2 , LiNi 0.8 Mn 0.1 Co 0.1 O 2 (NMC811), LiNi 0.92 Mn 0.04 Co 0.04O 2 , LiNi 0.85 Mn 0.075 Co 0.075 O 2 , LiNi 0.8 Co 0.15 Al 0.05 O 2 , LiNi 0.88 Co 0.1 Al 0.02 O 2 , LiNiO 2 (LNO) or a combination thereof.

[0121] In another embodiment, the cathode active material is LiCoO 2 , LiNiO 2 , LiMnO 2 , LiMn 2 O 4 Or Li 2 MnO 3 In a further embodiment, the cathode active material is LiNi 0.33 Mn 0.33 Co 0.33 O 2 , LiNi 0.4 Mn 0.4 Co 0.2 O 2 , LiNi 0.5 Mn 0.3 Co 0.2 O 2 , LiNi 0.6 Mn 0.2 Co 0.2 O 2 , LiNi 0.7 Mn 0.15 Co 0.15 O 2 , LiNi 0.7 Mn 0.1 Co 0.2 O 2 , LiNi 0.8 Mn 0.1 Co 0.1 O 2 , LiNi 0.92 Mn 0.04 Co 0.04 O 2 , LiNi 0.85 Mn 0.075 Co 0.075 O 2, LiNi 0.8 Co 0.15 Al 0.05 O 2 , or LiNi 0.88 Co 0.1 Al 0.02 O 2 isn't it.

[0122] In certain embodiments, the cathode active material is or includes a core-shell composite having a core and a shell structure, where the core is Li 1+x Ni a Mn b Co c Al (1-a-b-c) O 2 , LiCoO 2 , LiNiO 2 , LiMnO 2 , LiMn 2 O 4 , Li 2 MnO 3 , LiCrO 2 , Li 4 Ti 5 O 12 , LiV 2 O 5 , LiTiS 2 , LiMoS 2 , LiCo a Ni b O 2 , LiMn a Ni b O 2 , and combinations thereof; where -0.2≦x≦0.2, 0≦a<1, 0≦b<1, 0≦c<1, and a+b+c≦1. In some embodiments, the shell also comprises a lithium transition metal oxide. In certain embodiments, the lithium transition metal oxide of the shell is selected from the group of lithium transition metal oxides used for the core above. In other embodiments, the shell comprises a transition metal oxide. In certain embodiments, the transition metal oxide of the shell is Fe 2 O 3 , MnO 2 , Al 2 O 3 , MgO, ZnO, TiO 2, La 2 O 3 , CEO 2 , SnO 2 , ZrO 2 , RuO 2 and combinations thereof. In some embodiments, the shell comprises a lithium transition metal oxide and a transition metal oxide.

[0123] In some embodiments, the core and the shell each independently contain two or more lithium transition metal oxides. In some embodiments, one of the core or the shell contains only one lithium transition metal oxide, and the other contains two or more lithium transition metal oxides. The lithium transition metal oxide or oxides in the core and the shell may be the same, different, or partially different. In some embodiments, the two or more lithium transition metal oxides are uniformly distributed throughout the core. In some embodiments, the two or more lithium transition metal oxides are not uniformly distributed throughout the core.

[0124] In some embodiments, each of the metal oxides in the core and shell is independently doped with a dopant selected from the group consisting of Co, Cr, V, Mo, Nb, Pd, F, Na, Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge, and combinations thereof. In some embodiments, the cathode active material is not a core-shell composite.

[0125] In some embodiments, the electrode active material is a cathode active material for a sodium ion battery. In some embodiments, the cathode active material for a sodium ion battery is a cathode active material having the formula Na x M y A zwhere M is one or more metals and A is one or more anions including one or more of O, P, N, C, H, or halogen. In certain embodiments, the cathode active material for a sodium-ion battery is the sodium analog of the cathode active material described above, where lithium is replaced by sodium. In some embodiments, the cathode active material for a sodium-ion battery is NaCoO 2 , NaFeO 2 , NaNiO 2 , NaCrO 2 , NaVO 2 , and NaTiO 2 , NaFePO 4 , Na 3 V 2 (PO 4 ) 3 , Na 3 V 2 (PO 4 ) 2 F 3 , NMC type mixed oxides, and combinations thereof. In some embodiments, the cathode active material for a sodium-ion battery is an organic material such as disodium naphthalenediimide, a doped quinone, a pteridine derivative, a polyimide, a polyamic acid, or a combination thereof.

[0126] In some embodiments, the sodium-ion battery cathode active material is or includes a core-shell composite having a core and a shell structure. In some embodiments, the sodium-ion battery cathode active material is doped with a dopant. The same dopants as listed above for the lithium-ion battery cathode active material can be used to dope the sodium-ion battery cathode active material.

[0127] In some embodiments, the average diameter of the cathode active material particles is from about 0.1 μm to about 100 μm, from about 0.1 μm to about 50 μm, from about 0.5 μm to about 50 μm, from about 0.5 μm to about 30 μm, from about 0.5 μm to about 20 μm, from about 1 μm to about 20 μm, from about 2.5 μm to about 50 μm, from about 2.5 μm to about 20 μm, from about 5 μm to about 50 μm, from about 5 μm to about 20 μm, from about 7.5 μm to about 20 μm, from about 10 μm to about 50 μm, from about 10 μm to about 20 μm, from about 15 μm to about 50 μm, from about 15 μm to about 20 μm, from about 20 μm to about 50 μm, or from about 50 μm to about 100 μm.

[0128] In some embodiments, the average diameter of the cathode active material particles is less than 100 μm, less than 80 μm, less than 60 μm, less than 50 μm, less than 40 μm, less than 30 μm, less than 20 μm, less than 15 μm, less than 10 μm, less than 7.5 μm, less than 5 μm, less than 2.5 μm, less than 1 μm, less than 0.75 μm, or less than 0.5 μm. In some embodiments, the average diameter of the cathode active material particles is greater than 0.1 μm, greater than 0.25 μm, greater than 0.5 μm, greater than 0.75 μm, greater than 1 μm, greater than 2.5 μm, greater than 5 μm, greater than 7.5 μm, greater than 10 μm, greater than 15 μm, greater than 20 μm, greater than 30 μm, greater than 40 μm, or greater than 50 μm.

[0129] In some embodiments, the electrode active material is an anode active material. In some embodiments, the anode active material is a material selected from the group consisting of natural graphite particulate, synthetic graphite particulate, hard carbon, soft carbon, mesocarbon microbeads (MCMB), Sn particulate, SnO 2 , SnO, Li 4 Ti 5 O 12 The fine particles are selected from the group consisting of fine particles, Si fine particles, Si—C composite fine particles, and combinations thereof.

[0130] In some embodiments, the anode active material is doped with a metallic or non-metallic element. In some embodiments, the metallic element is selected from the group consisting of Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, and combinations thereof. In some embodiments, the non-metallic element is B, Si, Ge, N, P, F, S, Cl, I, Se, or combinations thereof.

[0131] In some embodiments, the anode active material is or comprises a core-shell composite having a core and a shell structure, the core and the shell being each independently selected from natural graphite particulate, synthetic graphite particulate, hard carbon, soft carbon, mesocarbon microbeads (MCMB), Sn particulate, SnO 2 , SnO, Li 4 Ti 5 O 12 The fine particles are selected from the group consisting of fine particles, Si fine particles, Si—C composite fine particles, and combinations thereof.

[0132] In some embodiments, the anode active material in the form of a core-shell composite comprises a core comprising a carbonaceous material and a shell coated on the carbonaceous material core. In some embodiments, the carbonaceous material is selected from the group consisting of soft carbon, hard carbon, natural graphite particulate, synthetic graphite particulate, mesocarbon microbeads, kish graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fibers, and combinations thereof. In some embodiments, the shell is selected from the group consisting of natural graphite particulate, synthetic graphite particulate, hard carbon, soft carbon, mesocarbon microbeads (MCMB), Sn particulate, SnO 2 , SnO, Li 4 Ti 5 O 12 The fine particles are selected from the group consisting of fine particles, Si fine particles, Si—C composite fine particles, and combinations thereof.

[0133] In some embodiments, the anode active material is not doped with a metallic or non-metallic element. In some embodiments, the anode active material is not doped with Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, B, Si, Ge, N, P, F, S, Cl, I, or Se.

[0134] In some embodiments, the electrode active material is an anode active material for a sodium ion battery. Although graphite is not preferred because the pores in the material are too small to hold sodium ions, many of the embodiments of anode active materials used in lithium ion batteries are also suitable for use as anode active materials for sodium ion batteries. Li 4 Ti 5 O 12 The microparticles are also not preferred as anode active materials for sodium ion batteries because lithium is present and is thought to affect the reaction mechanism in sodium ion batteries.

[0135] In some embodiments, the anode active material for a sodium ion battery is hard carbon, soft carbon, tin oxides such as SnO 2 and SnO, sodium titanates such as NaTi 2 (PO 4 ) 3 and Na 2 Ti 3 O 7 , SnS 2 , NbS 2 , SbO x , (0 < x ≦ 2), Sn-P compounds and composites, sodium alloys, and combinations thereof. In some embodiments, the anode active material for a sodium ion battery is a Prussian blue type sodium compound satisfying the formula Na x M y A z , where M is one or more metals and A is one or more anions containing one or more of O, P, N, C, H, or a halogen.

[0136] In some embodiments, the sodium-ion battery anode active material is or includes a core-shell composite having a core and a shell structure, hi some embodiments, the sodium-ion battery anode active material is doped with one or more elements selected from the group consisting of Sb, Sn, P, S, B, Al, Ga, In, Ge, Pb, As, Bi, Ti, Mo, Se, Te, Co, and combinations thereof.

[0137] In some embodiments, the aqueous solvent in the conductive composition is sufficient to act as the solvent for the entire electrode slurry. In such embodiments, no additional solvent is added to form the aqueous solvent of the electrode slurry. In other embodiments, additional aqueous solvent is further added to the aqueous solvent of the conductive composition to form the aqueous solvent of the electrode slurry.

[0138] In addition to promoting the dispersion of CNTs in aqueous solvents, the copolymer in the conductive composition of the present invention also exhibits exceptionally strong adhesive ability. One method for evaluating the adhesive strength of a polymeric material is to evaluate it by the adhesive strength between the polymeric material and a current collector.

[0139] In some embodiments, the adhesive strength between the copolymer and the current collector is from about 1 N / cm to about 10 N / cm, from about 1 N / cm to about 8 N / cm, from about 1 N / cm to about 5 N / cm, from about 1 N / cm to about 3 N / cm, from about 2 N / cm to about 10 N / cm, from about 2 N / cm to about 8 N / cm, from about 2 N / cm to about 5 N / cm, from about 3 N / cm to about 10 N / cm, from about 3 N / cm to about 8 N / cm, about 3 N / cm to about 6 N / cm, about 3 N / cm to about 5 N / cm, about 4 N / cm to about 10 N / cm, about 4 N / cm to about 8 N / cm, about 4 N / cm to about 6 N / cm, about 5 N / cm to about 10 N / cm, about 5 N / cm to about 8 N / cm, about 6 N / cm to about 10 N / cm, about 6 N / cm to about 8 N / cm, or about 7 N / cm to about 10 N / cm.

[0140] In some embodiments, the adhesive strength between the copolymer and the current collector is less than 10 N / cm, less than 9.5 N / cm, less than 9 N / cm, less than 8.5 N / cm, less than 8 N / cm, less than 7.5 N / cm, less than 7 N / cm, less than 6.5 N / cm, less than 6 N / cm, less than 5.5 N / cm, less than 5 N / cm, less than 4.5 N / cm, less than 4 N / cm, less than 3.5 N / cm, less than 3 N / cm, less than 2.5 N / cm, less than 2 N / cm, or less than 1.5 N / cm. In some embodiments, the adhesive strength between the copolymer and the current collector is greater than 1 N / cm, greater than 1.5 N / cm, greater than 2 N / cm, greater than 2.5 N / cm, greater than 3 N / cm, greater than 3.5 N / cm, greater than 4 N / cm, greater than 4.5 N / cm, greater than 5 N / cm, greater than 5.5 N / cm, greater than 6 N / cm, greater than 6.5 N / cm, greater than 7 N / cm, greater than 7.5 N / cm, greater than 8 N / cm, greater than 8.5 N / cm, greater than 9 N / cm, or greater than 9.5 N / cm.

[0141] The copolymer used to disperse the CNTs in the aqueous solvent of the conductive composition also has excellent binding ability, so that the copolymer can also act as a binder in the electrode layer of the electrode. The amount of copolymer present in the conductive composition is sufficient to bind the various electrode materials and to the current collector. Therefore, there is no need for an additional binder to be present in the electrode slurry. Therefore, a further advantage of the conductive composition of the present invention is that the use of said conductive composition in the electrode slurry will greatly simplify the composition of the electrode slurry and therefore the electrodes produced therefrom, as well as the manufacturing process of the electrodes. However, on the other hand, an additional binder may be introduced to enhance the binding ability of the electrode slurry to the current collector. There is no particular limit to the binder used, although the binder must have the desired properties as a binder and be compatible with the various components in the conductive composition so that the resulting electrode slurry is stable. Furthermore, it is preferred that the binder can be well dispersed in the electrode slurry to ensure a uniform and smooth coating. In some embodiments, the binder is aqueous in nature.

[0142] As described above, the conductive composition of the present invention can be used in an electrode slurry to improve the electrical conductivity of an electrode produced therefrom. In some embodiments, a conductive agent is also present in the electrode slurry to further improve the electrical conductivity of an electrode produced therefrom. In such embodiments, the conductive agent can be reduced as compared to electrode slurries known in the art, since CNTs are present in the electrode slurry and are particularly effective in improving the electrical conductivity of an electrode produced therefrom. Any suitable material can serve as the conductive agent. In some embodiments, the conductive agent is a carbonaceous material in the form of zero-dimensional carbon-based particles. CNTs have a shape synergy when used with zero-dimensional carbon-based particles, forming a three-dimensional conductive network that will help further improve the electrical contact between the various particles in the electrode. Non-limiting examples of suitable carbonaceous materials include carbon, carbon black, graphite, expanded graphite, graphene, graphene nanoplatelets, carbon fibers, carbon nanofibers, graphitized carbon flakes, carbon tubes, activated carbon, Super P, 0-dimensional KS6, 1-dimensional vapor grown carbon fibers (VGCF), mesoporous carbon, and combinations thereof.

[0143] In some embodiments, the conductive agent comprises a conductive polymer selected from the group consisting of polypyrrole, polyaniline, polyacetylene, polyphenylene sulfide (PPS), polyphenylene vinylene (PPV), poly(3,4-ethylenedioxythiophene) (PEDOT), polythiophene, and combinations thereof. In some embodiments, the conductive polymer simultaneously serves a dual role as a conductive agent as well as a binder. In other embodiments, the conductive agent does not comprise a conductive polymer.

[0144] In other embodiments, the CNTs in the conductive composition are sufficient to provide the electrode slurry, and any electrode produced therefrom, with excellent electrical conductivity, and thus in such embodiments, no conductive agent is present in the electrode slurry.

[0145] When a conductive agent is present in the electrode slurry, the weight ratio of CNT to conductive agent is important to realize full utilization of the synergistic effect of the conductive agent and CNT in the electrode. In certain embodiments, when a conductive agent is present in the electrode slurry, the weight ratio of CNTs to conductive agent is about 1% to about 35%, about 1% to about 30%, about 1% to about 25%, about 1% to about 20%, about 1% to about 18%, about 1% to about 16%, about 1% to about 10%, about 1% to about 8%, about 1% to about 5%, about 2% to about 35%, about 2% to about 30%, about 2% to about 25%, about 2% to about 20%, about 2% to about 15%, about 3% to about 20%, about 3% to about 15%, about 5% to about 25%, about 5% to about 20%, about 5% to about 15%, about 5% to about 10%, about 7% to about 20%, about 7% to about 15%, about 10% to about 20%, or about 10% to about 15%.

[0146] In some embodiments, when a conductive agent is present in the electrode slurry, the weight ratio of CNT to conductive agent is less than 35%, less than 30%, less than 25%, less than 20%, less than 18%, less than 16%, less than 14%, less than 12%, less than 10%, less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, or less than 4%. In some embodiments, when a conductive agent is present in the electrode slurry, the weight ratio of CNT to conductive agent is greater than 1%, greater than 2%, greater than 3%, greater than 4%, greater than 5%, greater than 6%, greater than 7%, greater than 8%, greater than 9%, greater than 10%, greater than 12%, greater than 14%, greater than 16%, greater than 18%, greater than 20%, greater than 22%, greater than 24%, or greater than 26%.

[0147] In some embodiments, the electrode slurry may further include other additives to improve electrode properties, hi some embodiments, the additives may include surfactants, dispersants and flexibility enhancing additives, salts, ion conducting polymers, and inorganic solid electrolytes.

[0148] In some embodiments, the amount of electrode active material in the electrode slurry is, by weight, based on the total weight of the electrode slurry, about 30% to about 70%, about 30% to about 65%, about 30% to about 60%, about 30% to about 55%, about 30% to about 50%, about 35% to about 70%, about 35% to about 65%, about 35% to about 60%, about 35% to about 55%, about 35% to about 50%, about 40% to about 70%, about 40% to about 65%, about 40% to about 60%, about 40% to about 55%, or about 40% to about 50%.

[0149] In some embodiments, the amount of electrode active material in the electrode slurry is at least 30%, at least 35%, at least 40%, at least 45%, at least 50%, at least 55%, at least 60%, or at least 65% by weight based on the total weight of the electrode slurry. In some embodiments, the amount of electrode active material in the electrode slurry is at most 70%, at most 65%, at most 60%, at most 55%, at most 50%, at most 45%, at most 40%, or at most 35% by weight based on the total weight of the electrode slurry.

[0150] In certain embodiments, the amount of CNTs in the electrode slurry may be, in weight percent based on the total weight of the electrode slurry, from about 0.01% to about 3.0%, from about 0.01% to about 2.5%, from about 0.01% to about 2%, from about 0.01% to about 1.8%, from about 0.01% to about 1.6%, from about 0.01% to about 1.4%, from about 0.001% to about 1.2%, from about 0.01% to about 1.0%, from about 0.01% to about 0.8%, from about 0.01% to about 0.6%, from about 0.01% to about 0.4%, from about 0.05% to about 3.0%, from about 0.05% to about 2.5%, from about 0. 05% to about 2%, about 0.05% to about 1.8%, about 0.05% to about 1.6%, about 0.05% to about 1.4%, about 0.05% to about 1.2%, about 0.05% to about 1.0%, about 0.05% to about 0.8%, about 0.05% to about 0.6%, about 0.05% to about 0.4%, about 0.1% to about 3.0%, about 0.1% to about 2.5%, about 0.1% to about 2%, about 0.1% to about 1.5%, about 0.1% to about 1.2%, about 0.1% to about 1.0%, about 0.1% to about 0.8%, or about 0.1% to about 0.6%.

[0151] In some embodiments, the amount of CNTs in the electrode slurry is less than 3.0%, less than 2.8%, less than 2.6%, less than 2.4%, less than 2.2%, less than 2.0%, less than 1.8%, less than 1.6%, less than 1.4%, less than 1.2%, less than 1.0%, less than 0.8%, less than 0.6%, or less than 0.4% by weight based on the total weight of the electrode slurry. In some embodiments, the amount of CNTs in the electrode slurry is greater than 0.01%, greater than 0.05%, greater than 0.1%, greater than 0.2%, greater than 0.4%, greater than 0.8%, greater than 1.2%, greater than 1.6%, greater than 2.0%, greater than 2.4%, or greater than 2.6% by weight based on the total weight of the electrode slurry.

[0152] In some embodiments, the amount of conductive agent in the electrode slurry is, in weight percent based on the total weight of the electrode slurry, about 0.1% to about 5%, about 0.1% to about 4.5%, about 0.1% to about 4%, about 0.1% to about 3.5%, about 0.1% to about 3%, about 0.1% to about 2%, about 0.1% to about 1%, about 0.1% to about 0.5%, about 0.5% to about 5%, about 0.5% to about 4.5%, about 0.5% to about 4%, about 0.5% to about 3.5%, about 0.5% to about 5 ... % to about 3%, about 0.5% to about 2.5%, about 0.5% to about 2%, about 1% to about 5%, about 1% to about 4.5%, about 1% to about 4%, about 1% to about 3.5%, about 1% to about 3%, about 1.5% to about 5%, about 1.5% to about 4.5%, about 1.5% to about 4%, about 1.5% to about 3.5%, about 1.5% to about 3%, about 2% to about 5%, about 2% to about 4.5%, about 2% to about 4%, about 2% to about 3.5%, or about 2% to about 3%. In other embodiments, the electrode slurry does not include any additional conductive agents other than the CNTs.

[0153] In some embodiments, the amount of conductive agent in the electrode slurry is less than 5%, less than 4.5%, less than 4%, less than 3.5%, less than 3%, less than 2.5%, less than 2%, less than 1.5%, less than 1%, or less than 0.5% by weight based on the total weight of the electrode slurry. In some embodiments, the amount of conductive agent in the electrode slurry is greater than 0%, greater than 0.5%, greater than 1%, greater than 1.5%, greater than 2%, greater than 2.5%, greater than 3%, greater than 3.5%, greater than 4%, or greater than 4.5% by weight based on the total weight of the electrode slurry.

[0154] In some embodiments, the amount of binder in the electrode slurry is, by weight percent based on the total weight of the electrode slurry, about 0.1% to about 5%, about 0.1% to about 4%, about 0.1% to about 3%, about 0.1% to about 2%, about 0.5% to about 5%, about 0.5% to about 4%, about 0.5% to about 3%, about 0.5% to about 2%, about 1% to about 5%, about 1% to about 4%, about 1% to about 3%, or about 1% to about 2%. In other embodiments, the electrode slurry does not include a binder.

[0155] In some embodiments, the amount of binder in the electrode slurry is less than 5%, less than 4%, less than 3%, less than 2%, less than 1.8%, less than 1.6%, less than 1.4%, less than 1.2%, less than 1%, less than 0.8%, less than 0.6%, or less than 0.4% by weight based on the total weight of the electrode slurry. In some embodiments, the amount of binder in the electrode slurry is greater than 0%, greater than 0.25%, greater than 0.5%, greater than 0.75%, greater than 1%, greater than 1.2%, greater than 1.4%, greater than 1.6%, greater than 1.8%, greater than 2%, greater than 3%, or greater than 4% by weight based on the total weight of the electrode slurry.

[0156] In some embodiments, the solids content of the electrode slurry is about 35% to about 80%, about 35% to about 75%, about 35% to about 70%, about 35% to about 65%, about 35% to about 60%, about 35% to about 55%, about 40% to about 80%, about 40% to about 75%, about 40% to about 70%, about 40% to about 65%, about 40% to about 60%, about 45% to about 80%, about 45% to about 75%, about 45% to about 70%, or about 45% to about 65% by weight, based on the total weight of the electrode slurry.

[0157] In some embodiments, the solids content of the electrode slurry is at least 35%, at least 40%, at least 45%, at least 50%, at least 55%, at least 60%, at least 65%, or at least 70% by weight based on the total weight of the electrode slurry. In some embodiments, the solids content of the electrode slurry is less than 75%, less than 70%, less than 65%, less than 60%, less than 55%, less than 50%, less than 45%, or less than 40% by weight based on the total weight of the electrode slurry.

[0158] The electrode slurries of the present invention can have a higher solids content than conventional electrode slurries, which allows for more electrode active material to be prepared at any one time for subsequent processing, thus improving efficiency and maximizing productivity.

[0159] The method used to prepare the electrode slurry from the various electrode components is not particularly limited, except that all electrode components must be mixed to form a homogenous electrode slurry, for example, by mixing in a homogenizer. In some embodiments, all materials used to prepare the electrode slurry are added to the homogenizer in a single batch. In other embodiments, each electrode component of the electrode slurry can be added to the homogenizer in one or more batches, each batch may include one or more electrode components. Any homogenizer that can reduce or eliminate particle agglomeration and / or promote homogenous distribution of the electrode components in the electrode slurry can be used herein. Homogeneous distribution plays an important role in making a battery with good battery performance. In some embodiments, the homogenizer is a planetary agitation mixer, an agitation mixer, or a blender.

[0160] There is no particular limit to the conditions used to form the electrode slurry, but such conditions should be sufficient to produce a homogenous slurry in which the electrode components within the slurry are well dispersed. There is no particular limit to the time taken, temperature, or agitation speed used to homogenize the electrode slurry, except that the time, temperature, and agitation speed should be sufficient to ensure homogenous distribution of the various electrode components in the electrode slurry.

[0161] In some embodiments, after the electrode slurry is homogenized, the electrode slurry can be coated on one or both sides of a current collector to form an electrode layer. The current collector serves to collect electrons generated by the electrochemical reaction of the cathode active material or to provide electrons required for the electrochemical reaction. In some embodiments, the current collector may be in the form of a foil, sheet or film. In some embodiments, the current collector is a metal. In some embodiments, the current collector is selected from the group consisting of stainless steel, titanium, nickel, aluminum, copper, platinum, gold, silver, chromium, zirconium, tungsten, molybdenum, silicon, tin, vanadium, zinc, cadmium, or alloys thereof. In some embodiments, the current collector further comprises a conductive resin.

[0162] In some embodiments, the current collector has a two-layer structure including an outer layer and an inner layer, the outer layer includes a conductive material, and the inner layer includes an insulating material or another conductive material; for example, a polymeric insulating material coated with an aluminum layer or aluminum with a conductive resin layer. In some embodiments, the conductive material is selected from the group consisting of stainless steel, titanium, nickel, aluminum, copper, platinum, gold, silver, chromium, zirconium, tungsten, molybdenum, silicon, tin, vanadium, zinc, cadmium, or alloys thereof, conductive resins, and combinations thereof.

[0163] In some embodiments, the current collector has a three-layer structure including an outer layer, an intermediate layer, and an inner layer, the outer layer and the inner layer include a conductive material, and the intermediate layer includes an insulating material or another conductive material; for example, a plastic material coated with a metal layer on both sides. In some embodiments, each of the outer layer, the intermediate layer, and the inner layer is independently stainless steel, titanium, nickel, aluminum, copper, platinum, gold, silver, chromium, zirconium, tungsten, molybdenum, silicon, tin, vanadium, zinc, cadmium, or alloys thereof, conductive resin, or a combination thereof.

[0164] In some embodiments, the insulating material is a polymeric material selected from the group consisting of polycarbonate, polyacrylate, polyacrylonitrile, polyester, polyamide, polystyrene, polyurethane, polyepoxy, poly(acrylonitrile butadiene styrene), polyimide, polyolefin, polyethylene, polypropylene, polyphenylene sulfide, poly(vinyl ester), polyvinyl chloride, polyether, polyphenylene oxide, cellulose polymer, and combinations thereof. In some embodiments, the current collector has three or more layers. In some embodiments, the current collector is coated with a protective coating. In some embodiments, the protective coating comprises a carbon-containing material. In some embodiments, the current collector is not coated with a protective coating.

[0165] In some embodiments, a conductive layer can be coated on the current collector to improve its electrical current conductivity. In certain embodiments, the conductive layer comprises a material selected from the group consisting of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanoplatelets, carbon fibers, carbon nanofibers, graphitized carbon flakes, carbon tubes, carbon nanotubes, activated carbon, mesoporous carbon, and combinations thereof.

[0166] The thickness of the conductive layer affects the volume that the current collector occupies in the battery, and thus the thickness of the electrode, which in turn affects the capacity in the battery. In some embodiments, the thickness of the conductive layer on the current collector is about 0.5 μm to about 5.0 μm, about 1.0 μm to about 4.0 μm, about 1.0 μm to about 3.0 μm, about 1.5 μm to about 2.0 μm, about 1.0 μm to about 1.8 μm, about 1.2 μm to about 1.8 μm, or about 1.0 μm to about 1.5 μm. In some embodiments, the thickness of the conductive layer on the current collector is less than 5.0 μm, less than 4.0 μm, less than 3.0 μm, less than 2.0 μm, or less than 1.5 μm. In some embodiments, the thickness of the conductive layer on the current collector is greater than 0.5 μm, greater than 1.0 μm, greater than 1.5 μm, greater than 2.0 μm, greater than 2.5 μm, greater than 3.0 μm, or greater than 3.5 μm.

[0167] The thickness of the current collector affects the volume it occupies in the battery, the thickness of the electrode, and therefore the capacity in the battery. In some embodiments, the current collector has a thickness of about 5 μm to about 30 μm, about 5 μm to about 20 μm, about 5 μm to about 15 μm, about 10 μm to about 30 μm, about 10 μm to about 25 μm, or about 10 μm to about 20 μm.

[0168] In some embodiments, the current collector has a thickness of less than 30 μm, less than 28 μm, less than 26 μm, less than 24 μm, less than 22 μm, less than 20 μm, less than 18 μm, less than 16 μm, less than 14 μm, less than 12 μm, less than 10 μm, less than 8 μm, or less than 6 μm. In some embodiments, the current collector is thicker than 5 μm, thicker than 7 μm, thicker than 10 μm, thicker than 12 μm, thicker than 14 μm, thicker than 16 μm, thicker than 18 μm, thicker than 20 μm, thicker than 22 μm, thicker than 24 μm, thicker than 26 μm, or thicker than 28 μm.

[0169] The apparatus and conditions used for coating the electrode slurry on the current collector to form the electrode layer are not particularly limited, except that a uniform, flat, and smooth electrode layer film must be formed. In some embodiments, the coating process is performed using a doctor blade coater, a slot die coater, a transfer coater, a spray coater, a roll coater, a gravure coater, a dip coater, or a curtain coater. In some embodiments, the electrode slurry is coated directly onto the current collector. In other embodiments, the electrode slurry is first coated onto a release film to form a free-standing electrode layer. The free-standing electrode layer is then combined with the current collector and pressed to form the electrode layer.

[0170] In some embodiments, following coating of the electrode slurry onto the current collector of the present invention, the coating is dried. Any device capable of drying the coating can be used herein to apply the electrode layer onto the current collector.

[0171] The conditions used for drying are not particularly limited, except that the drying conditions must be sufficient to ensure that the electrode layer is strongly adhered to the current collector. However, drying the electrode slurry at a temperature above 100° C. may cause undesirable deformation of the electrode, thereby affecting the performance of the resulting electrode. In some embodiments, the resulting electrode after drying of the film is mechanically compressed to increase the density of the electrode.

[0172] In certain embodiments, the thickness of the electrode layer on the current collector is from about 10 μm to about 90 μm, from about 10 μm to about 80 μm, from about 10 μm to about 70 μm, from about 10 μm to about 60 μm, from about 10 μm to about 50 μm, from about 10 μm to about 40 μm, from about 10 μm to about 30 μm, from about 10 μm to about 20 μm, from about 25 μm to about 75 μm, from about 25 μm to about 50 μm, from about 30 μm to about 90 μm, from about 30 μm to about 80 μm, from about 35 μm to about 90 μm, from about 35 μm to about 85 μm, from about 35 μm to about 80 μm, or from about 35 μm to about 75 μm.

[0173] In some embodiments, the thickness of the electrode layer on the current collector is less than 25 μm, less than 30 μm, less than 35 μm, less than 40 μm, less than 45 μm, less than 50 μm, less than 55 μm, less than 60 μm, less than 65 μm, less than 70 μm, less than 75 μm, less than 80 μm, less than 85 μm, or less than 90 μm. In some embodiments, the thickness of the electrode layer on the current collector is greater than 10 μm, greater than 15 μm, greater than 20 μm, greater than 25 μm, greater than 30 μm, greater than 35 μm, greater than 40 μm, greater than 45 μm, greater than 50 μm, greater than 55 μm, greater than 60 μm, greater than 65 μm, greater than 70 μm, greater than 75 μm, or greater than 80 μm.

[0174] In some embodiments, the areal density of the electrode layer on the current collector is about 1 mg / cm 2 to about 40 mg / cm 2 , about 1mg / cm 2 to about 30 mg / cm 2 , about 1mg / cm 2 to about 20 mg / cm 2 , about 3mg / cm 2 to about 40 mg / cm 2 , about 3mg / cm 2 to about 30 mg / cm 2 , about 3mg / cm 2 to about 20 mg / cm 2 , about 5mg / cm 2 to about 40 mg / cm 2 , about 5mg / cm 2 to about 30 mg / cm 2 , about 5mg / cm 2 to about 20 mg / cm 2 , about 8mg / cm 2 to about 40 mg / cm 2 , about 8mg / cm 2 to about 30 mg / cm 2 , about 8mg / cm 2 to about 20 mg / cm 2 , about 10mg / cm 2 to about 40 mg / cm 2 , about 10mg / cm 2 to about 30 mg / cm 2 , about 10mg / cm2 to about 20 mg / cm 2 , about 15mg / cm 2 to about 40 mg / cm 2 , or about 20 mg / cm 2 to about 40 mg / cm 2 It is.

[0175] In some embodiments, the areal density of the electrode layer on the current collector is less than 1 mg / cm 2 Higher or 5mg / cm 2 Higher or 10mg / cm 2 Higher or 15mg / cm 2 Higher or 20mg / cm 2 Higher or 25mg / cm 2 Higher or 30mg / cm 2 Higher or 35 mg / cm 2 In some embodiments, the areal density of the electrode layer on the current collector is 40 mg / cm 2 Less than 35 mg / cm 2 Less than 30 mg / cm 2 Less than 25 mg / cm 2 Less than 20 mg / cm 2 Less than 15 mg / cm 2 Less than 10 mg / cm 2 Less than 5 mg / cm 2 is less than.

[0176] Furthermore, the binder applied in the present invention (i.e., the copolymer in the conductive composition and, optionally, the binding agent) allows the electrode layer to adhere to the current collector of the electrode. It is important that the electrode layer has good peel strength to the current collector, since the peel strength has a large effect on the mechanical stability of the electrode and the cyclability of the battery. Therefore, the electrode must have sufficient peel strength to withstand the rigors of battery manufacturing. In some embodiments, the peel strength between the current collector and the electrode layer is from about 1.0 N / cm to about 8.0 N / cm, from about 1.0 N / cm to about 6.0 N / cm, from about 1.0 N / cm to about 5.0 N / cm, from about 1.0 N / cm to about 4.0 N / cm, from about 1.0 N / cm to about 3.0 N / cm, from about 1.0 N / cm to about 2.5 N / cm, from about 1.0 N / cm to about 2.0 N / cm, from about 1.2 N / cm to about 3.0 N / cm, from about 1.2 N / cm to about 2.5 N / cm, from about 1.2 N / cm to about 2.0 N / cm, from about 1.5 N / cm to about 3.0 N / cm, from about 1.5 N / cm to about 2.5 ... to about 2.5 N / cm, about 1.5 N / cm to about 2.0 N / cm, about 1.8 N / cm to about 3.0 N / cm, about 1.8 N / cm to about 2.5 N / cm, about 2.0 N / cm to about 6.0 N / cm, about 2.0 N / cm to about 5.0 N / cm, about 2.0 N / cm to about 3.0 N / cm, about 2.0 N / cm to about 2.5 N / cm, about 2.2 N / cm to about 3.0 N / cm, about 2.5 N / cm to about 3.0 N / cm, about 3.0 N / cm to about 8.0 N / cm, about 3.0 N / cm to about 6.0 N / cm, or about 4.0 N / cm to about 6.0 N / cm.

[0177] In some embodiments, the peel strength between the current collector and the electrode layer is 1.0 N / cm or more, 1.2 N / cm or more, 1.5 N / cm or more, 2.0 N / cm or more, 2.2 N / cm or more, 2.5 N / cm or more, 3.0 N / cm or more, 3.5 N / cm or more, 4.0 N / cm or more, 4.5 N / cm or more, 5.0 N / cm or more, 5.5 N / cm or more, 6.0 N / cm or more, 6.5 N / cm or more, 7.0 N / cm or more, or 7.5 N / cm or more. In some embodiments, the peel strength between the current collector and the electrode layer is less than 8.0 N / cm, less than 7.5 N / cm, less than 7.0 N / cm, less than 6.5 N / cm, less than 6.0 N / cm, less than 5.5 N / cm, less than 5.0 N / cm, less than 4.5 N / cm, less than 4.0 N / cm, less than 3.5 N / cm, less than 3.0 N / cm, less than 2.8 N / cm, less than 2.5 N / cm, less than 2.2 N / cm, less than 2.0 N / cm, less than 1.8 N / cm, or less than 1.5 N / cm.

[0178] In some embodiments, an electrode slurry comprising the conductive composition of the present invention may be used to fabricate an electrode, which may then be assembled with a counter electrode and an electrolyte to form a battery. When the electrode is a cathode, the counter electrode is an anode; when the electrode is an anode, the counter electrode is a cathode.

[0179] In some embodiments, the electrolyte is a liquid electrolyte. Such a liquid electrolyte includes an electrolyte solvent and a salt. In some embodiments, the electrolyte solvent is water. In other embodiments, the electrolyte solvent is a liquid comprised of one or more organic solvents. Some non-limiting examples of organic solvents include dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate methyl acetate, methyl propanoate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran methyl bromide, ethyl bromide, methyl formate, acetonitrile, dimethyl sulfoxide, dimethylformamide, N-methyl-2-pyrrolidone, and combinations thereof.

[0180] In some embodiments, the salt of the liquid electrolyte is a lithium salt. Some non-limiting examples of the lithium salt include LiPF 6 , LiBO 2 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiAlCl 4 , LiClO 4 , LiCl, LiI, LiNO 3 , LiB(C 2 O 4 ) 2 , LiSO 3 CF 3 , LiN(SO 2 F) 2 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 CF 2 CF 3 ) 2 , LiC 2 H 3 O 2 , and combinations thereof.

[0181] In some embodiments, the salt of the liquid electrolyte is a sodium salt. In some embodiments, the sodium salt is a sodium analog of the lithium salts mentioned above, where the lithium is replaced by sodium. Such sodium salts include NaPF 6 , NaBF 4 , NaN(SO 2 CF 3 ) 2 , NaN(SO 2 F) 2 , NaClO 4 , and NaSO 3 CF 3 In some embodiments, the sodium salt has the formula NaMF x where x=4 or 6, respectively, and each M is one or more salts of Al 3+ , B 3+ , Ga 3+ , In 3+ , Sc 3+ , Y 3+ , La 3+ , P 5+ , As 5+ is selected from the group consisting of:

[0182] In some embodiments, the electrolyte is a solid electrolyte. In some embodiments, the solid electrolyte is a polymer electrolyte. Such a polymer electrolyte includes an ion-conducting polymer and a salt. In some embodiments, the salt of the polymer electrolyte is one or more lithium salts or one or more sodium salts described above.

[0183] In some embodiments, the solid electrolyte is an inorganic solid electrolyte. In some embodiments, the inorganic solid electrolyte is for use in a solid-state lithium ion battery. In some embodiments, the inorganic solid electrolyte for a solid-state lithium ion battery is an inorganic solid electrolyte, such as an LPS sulfide containing sulfur and phosphorus, lithium-phosphorus-iodine-oxygen sulfide; lithium-phosphorus-oxygen sulfide; lithium-zinc-germanium sulfide; lithium-germanium-sulfide; LLTO-based compounds; perovskite compounds; NASICON compounds; lithium-aluminum-titanium-silicon phosphate; lithium-aluminum oxide; lithium-vanadium-germanium oxide; lithium-zinc-germanium oxide; lithium-lanthanum-zirconium oxide; lithium-lanthanum-zirconium-aluminum oxide; lithium-lanthanum-zirconium-tantalum oxide; Li 3 N; lithium-aluminum chloride; and combinations thereof.

[0184] In some embodiments, the inorganic solid electrolyte is for use in a solid-state sodium ion battery. In some embodiments, the inorganic solid electrolyte for the solid-state sodium ion battery is a sodium analog of the inorganic solid electrolyte suitable for use in the solid-state lithium ion battery described above, where lithium is replaced by sodium. In some embodiments, the inorganic solid electrolyte for the solid-state sodium ion battery is a NASICON type inorganic solid electrolyte, a NaPS sulfide containing sulfur and phosphorus, a sodium polyaluminate, and combinations thereof.

[0185] In some embodiments, the solid electrolyte is a gel electrolyte. Such gel electrolytes include the polymer electrolytes described above, as well as the electrolyte solvents described above.

[0186] As described above, the adhesion of the CNTs to the copolymer and subsequent solvation of the CNT-copolymer composite allows the CNTs to be well dispersed in the aqueous medium of the conductive composition. Moreover, the conductive composition remains stable even after a significant amount of time has passed. Thus, the conductive composition of the present invention allows for much easier processing and handling of CNTs while retaining excellent CNT performance. The conductive composition of the present invention can therefore be used in any existing or potential application of CNTs, such as batteries. More specifically, the conductive composition is highly suitable for use in an aqueous solvent-based electrode slurry that includes an electrode active material in addition to the conductive composition. The electrode slurry may further include a conductive agent, additional aqueous solvent, and / or a binder, although a binder may not be specifically required since the copolymer in the conductive composition may also act as a binder in the electrode slurry. Thus, the development of an aqueous-based slurry that includes CNTs with a simple composition and without degrading battery performance such as cyclability and capacity is achieved by the present invention. Batteries including electrodes prepared using the present invention exhibit high cycle stability.

[0187] The following examples are presented to illustrate the embodiments of the present invention, but are not intended to limit the present invention to the specific embodiments described. Unless otherwise indicated, all ratios and percentages are by weight. All numerical values ​​are approximate. When numerical ranges are given, it should be understood that embodiments outside the stated ranges may still fall within the scope of the present invention. The specific details described in each example should not be construed as essential features of the present invention.

[0188] The present invention has been described with respect to a limited number of embodiments, and the specific features of one embodiment should not be attributed to other embodiments of the invention. In some embodiments, the method may include numerous steps not described herein. In other embodiments, the method does not include, or is substantially free of, steps not recited herein. Variations and modifications from the described embodiments exist. It is intended that the appended claims cover all such modifications and variations as being within the scope of the present invention. Working Example

[0189] The pH value of the conductive composition was measured using an electrode-type pH meter (ION 2700, Eutech Instruments).

[0190] The dynamic viscosity of the conductive composition was measured at 22° C. using a HAAKE® Viscotester® iQ (Thermo Fisher Scientific).

[0191] The resistance of the conductive composition was measured using an ohmmeter (UT204A, Uni Trend Technology China Co. Ltd., China). The conductive composition was applied to a glass slide to a thickness of 0.5 mm, and then dried using an electric oven at 70°C. The drying time was about 30 minutes, and the thickness of the resulting conductive layer was about 0.02 mm. The two probes of the ohmmeter were placed at two points on the conductive layer with a 10 mm gap between them. The measurement was repeated three times, and the average value was calculated.

[0192] The stability of the conductive composition was evaluated by observation. 3 A sample of the conductive composition was transferred into a beaker and the beaker was sealed. The sealed beaker was then left at room temperature for one week. If no precipitation was observed after one week, indicating no aggregation of CNTs had occurred, and the conductive composition remained homogeneous, the conductive composition was considered stable.

[0193] The adhesive strength of the dried copolymer dispersion was measured with a tensile tester (DZ-106A, obtained from Dongguan Zonhow Test Equipment Co. Ltd., China). This test measures the average force in Newtons required to peel the copolymer layer from the current collector at an angle of 180°. The mean roughness depth (Rz) of the current collector is 2 μm. The copolymer was coated on the current collector and allowed to dry to obtain a layer with a thickness of 10 μm to 12 μm. The coated current collector was then placed in a constant temperature of 25°C and constant humidity of 50% for 30 minutes. A piece of adhesive tape (3M; USA; model no. 810) with a width of 18 mm and a length of 20 mm was attached to the surface of the binder layer. The binder strip was clamped in the testing machine, the tape was folded at 180° and set in the moveable jaw, and pulled at a peel speed of 100 mm per minute at room temperature. The maximum peel strength was recorded as the adhesive strength. The measurement was repeated three times and the average value was calculated. Example 1 A) Preparation of the copolymer

[0194] To a round bottom flask containing 1140 g of distilled water, 22.34 g of sodium hydroxide (NaOH) was added. The mixture was stirred at 80 rpm for 30 minutes to obtain a first suspension.

[0195] 50.29 g of acrylic acid was added to the first suspension. The mixture was further stirred at 80 rpm for 30 minutes to obtain a second suspension.

[0196] 21.57 g of acrylamide was dissolved in 30 g of DI water to obtain an acrylamide solution. Then, 51.57 g of the acrylamide solution was added to the second suspension. The mixture was further heated to 55° C. and stirred at 80 rpm for 45 minutes to obtain a third suspension.

[0197] 107.88 g of acrylonitrile was added to the third suspension. The mixture was further stirred at 80 rpm for 10 minutes to obtain a fourth suspension.

[0198] Further, 0.045 g of a water-soluble free radical initiator (ammonium persulfate, APS; obtained from Aladdin Industries Corporation, China) was dissolved in 9 g of deionized water, and 0.0225 g of a reducing agent (sodium bisulfite; obtained from Tianjin Damao Chemical Reagent Factory, China) was dissolved in 4.5 g of deionized water. 9.045 g of the APS solution and 4.5225 g of the sodium bisulfite solution were added to the fourth suspension. The mixture was stirred at 55° C. and 200 rpm for 24 hours to obtain a fifth suspension.

[0199] After the reaction was completed, the temperature of the fifth suspension was lowered to 25°C. 11.16g of NaOH was dissolved in 1200g of deionized water. Then, 1211.16g of sodium hydroxide solution was added dropwise to the fifth suspension. The fifth suspension was filtered through a 200μm nylon mesh. The copolymer was successfully prepared and was in the form of a water dispersion. The weight average molecular weight of the copolymer was about 153,000g / mol, and the solid content of the copolymer dispersion was 7.69wt.%. The adhesive strength between the copolymer and the current collector was 3.40N / cm. B) Preparation of the Conductive Composition

[0200] 1755.5 g of the copolymer dispersion of Example 1 (solid content 7.69 wt.%) was added to 1231.0 g of deionized water while stirring with an overhead stirrer (R20, IKA). After addition, the mixture was further stirred at 25° C. and a speed of 500 rpm for about 10 minutes to form a first composition.

[0201] 13.5 g of dry powdered CNTs (obtained from Jiangsu Cnano Technology Co. Ltd., China) were added to the first composition. The CNTs had an average diameter of 7 to 11 nm, an average length of 50 to 250 μm, and a BET specific surface area of ​​250 to 350 m. 2 After the addition, the mixture was further stirred at 500 rpm for about 15 minutes at 25° C. to form a second composition.

[0202] After the formation of the second composition, the second composition was transferred to a sand mill (CNT-T1L, KANGBO Machinery Co. Ltd., China). The second composition was further ground at a speed of 2000 rpm for about 2 hours at 25° C. to form a conductive composition. The pH of the conductive composition was about 7.3.

[0203] Example 1 was repeated three more times with minor changes to the CNT specifications.

[0204] In the first iteration, the average diameter of the CNTs was 7 to 11 nm, the average length was 5 to 20 μm, and the BET specific surface area was 200 to 300 m. 2 / g.

[0205] In the second iteration, the average diameter of the CNTs was 2.4 nm, the average length was about 500 μm, and the BET specific surface area was about 450 m. 2 / g.

[0206] In the third iteration, the average diameter of the CNTs was 10 to 25 nm, the average length was about 10 μm, and the BET specific surface area was 110 to 250 m. 2 / g. C) Preparation of the positive electrode

[0207] A first mixture was prepared by dispersing 7.8 g of a conductive agent (SuperP; available from Timcal Ltd, Bodio, Switzerland) in 200 g of the conductive composition of Example 1 while stirring with an overhead stirrer (R20, IKA). After addition, the first mixture was further stirred at 25° C. and a speed of 1,200 rpm for about 30 minutes.

[0208] A second mixture was then prepared by adding 276 g of NMC811 (obtained from Shandong Tianjiao New Energy Co., Ltd, China) to the first mixture at 25° C. while stirring with an overhead stirrer. The second mixture was then degassed for 1 h under a pressure of about 10 kPa. The second mixture was further stirred at 25° C. and a speed of 1,200 rpm for about 60 min to form a homogenized cathode slurry.

[0209] The homogenized cathode slurry was applied to both sides of the surface of the current collector prepared above using a doctor blade coater with a gap width of 120 μm. The slurry applied to the current collector in a thickness of 80 μm was dried at 85 °C using an electric oven to form a cathode layer. The drying time was about 20 minutes. The electrode was then pressed to reduce the thickness of the cathode layer to 50 μm. The surface density of the cathode layer on the current collector was 16.00 mg / cm. 2 It is. D) Coin Cell Assembly

[0210] The electrochemical performance of the above prepared cathode was tested in a CR2032 coin Li cell assembled in an argon-filled glove box. The cathode was cut into a disk for coin cell assembly. A lithium metal foil with a thickness of 500 μm was used as the counter electrode. The cathode and counter electrode were kept separate by a separator. The separator was a ceramic-coated, non-woven (MPM, Japan) microporous membrane with a thickness of about 25 μm. The electrode assembly was then dried in a box-type resistance oven under vacuum (DZF-6020, obtained from Shenzhen Kejing Star Technology Co. Ltd., China) at 105 °C for about 16 h.

[0211] The electrolyte was then poured into the container holding the packed electrodes under a high-purity argon atmosphere with moisture and oxygen contents each below 3 ppm. The electrolyte was LiPF 2 in a 1:1:1 volumetric mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). 6 The solution contained (1 M) of electrolyte. After electrolyte filling, the coin cells were mechanically pressed using a standard circular shaped punch tooling. E) Performance measurement

[0212] The dynamic viscosity and resistance of the conductive composition were measured. Next, the stability performance of the conductive composition was evaluated. The performance measurement results of the conductive composition of Example 1 are shown in Table 1 below, where the conductive composition recognized as stable is represented by "Y" and the conductive composition recognized as not stable is represented by "N".

[0213] The viscosity, resistance, and stability of the conductive compositions containing various iterative specifications of CTN were also measured, and these conductive compositions were found to have similar performance and properties to the conductive composition of Example 1.

[0214] The coin cells were analyzed using a multi-channel battery tester (BTS-4008-5V10mA, obtained from Neware Electronics Co., Ltd, China) with constant current. After one cycle at C / 20, they were charged and discharged at a rate of C / 2. The charge / discharge cycle test of the cells was performed between 3.0 and 4.3V at 25°C and a current density of C / 2 to determine the discharge capacity. The electrochemical performance of the coin cells of Example 1 was measured and is shown in Table 1 below.

[0215] The performance of coin cells containing conductive compositions with various repeat specifications of CTN was also measured, and these conductive compositions were found to have similar performance to the conductive composition of Example 1. Preparation of the Conductive Composition of Example 2 A) Preparation of the copolymer

[0216] The copolymer dispersions were prepared as described in Example 1, except that 25.98 g of sodium hydroxide was added in the preparation of the first suspension, 56.85 g of acrylic acid was added in the preparation of the second suspension, 38.82 g of acrylamide was added in the preparation of the third suspension, and 90.17 g of acrylonitrile was added in the preparation of the fourth suspension. The weight average molecular weight of the copolymer was about 158,000 g / mol, and the solids content of the copolymer dispersion was 8.07 wt.%. B) Preparation of the Conductive Composition

[0217] A conductive composition was prepared as described in Example 1, except that in preparing the first composition, 1672.9 g of the copolymer dispersion of Example 2 (8.07 wt.% solids) was added to 1313.6 g of deionized water. The pH of the conductive composition was about 7.6. Preparation of the Conductive Composition of Example 3 A) Preparation of the copolymer

[0218] The copolymer dispersions were prepared as described in Example 1, except that 36.91 g of sodium hydroxide was added in the preparation of the first suspension, 76.53 g of acrylic acid was added in the preparation of the second suspension, 43.14 g of acrylamide was added in the preparation of the third suspension, and 72.46 g of acrylonitrile was added in the preparation of the fourth suspension. The weight average molecular weight of the copolymer was about 161,000 g / mol, and the solids content of the copolymer dispersion was about 8.23 ​​wt.%. B) Preparation of the Conductive Composition

[0219] A conductive composition was prepared as described in Example 1, except that in preparing the first composition, 1640.3 g of the copolymer dispersion of Example 3 (8.23 wt.% solids) was added to 1346.2 g of deionized water. The pH of the conductive composition was about 7.4. Preparation of the Conductive Composition of Example 4 A) Preparation of the copolymer

[0220] The copolymer dispersions were prepared as described in Example 1, except that 55.11 g of sodium hydroxide was added in the preparation of the first suspension, 109.33 g of acrylic acid was added in the preparation of the second suspension, 21.57 g of acrylamide was added in the preparation of the third suspension, and 64.40 g of acrylonitrile was added in the preparation of the fourth suspension. The weight average molecular weight of the copolymer was about 167,000 g / mol, and the solids content of the copolymer dispersion was about 8.90 wt %. B) Preparation of the Conductive Composition

[0221] A conductive composition was prepared as described in Example 1, except that in preparing the first composition, 1516.9 g of the copolymer dispersion of Example 4 (8.90 wt.% solids) was added to 1469.7 g of deionized water. The pH of the conductive composition was about 7.1. Preparation of the Conductive Composition of Example 5

[0222] The conductive compositions were prepared as described in Example 1, except that 2496.8 g of the copolymer dispersion of Example 1 (7.69 wt.% solids) was added to 484.1 g of deionized water in the preparation of the first composition, and 19.2 g of CNTs was added in the preparation of the second composition. The pH of the conductive compositions was about 7.3. Preparation of the Conductive Composition of Example 6

[0223] The conductive compositions were prepared as described in Example 1, except that 1950.6 g of the copolymer dispersion of Example 1 (7.69 wt.% solids) was added to 1041.9 g of deionized water in the preparation of the first composition, and 7.5 g of CNTs was added in the preparation of the second composition. The pH of the conductive compositions was about 7.5. Preparation of the Conductive Composition of Example 7

[0224] The conductive compositions were prepared as described in Example 1, except that 2535.8 g of the copolymer dispersion of Example 1 (7.69 wt.% solids) was added to 425.2 g of deionized water in the preparation of the first composition, and 39 g of CNTs was added in the preparation of the second composition. The pH of the conductive compositions was about 7.9. Preparation of the Conductive Composition of Example 8

[0225] A conductive composition was prepared as described in Example 1, except that additional 0.01 M sodium hydroxide was added to the second composition to raise the pH of the conductive composition to about 8.5. Preparation of the Conductive Composition of Example 9

[0226] A conductive composition was prepared as described in Example 1, except that additional 0.01 M sodium hydroxide was added to the second composition to raise the pH of the conductive composition to about 9.5. Preparation of Positive Electrodes of Examples 2 to 9

[0227] Positive electrodes were prepared by the method described in Example 1, except that the respective conductive compositions were used in place of the conductive composition of Example 1 in preparing the cathode slurry. Preparation of coin cells for Examples 2 to 9

[0228] Coin cells were prepared as described in Example 1. Performance measurements for Examples 2 to 9

[0229] The performance measurements were carried out in the same manner as described in Example 1. The performance measurement results of the conductive compositions of Examples 2 to 9 are shown in Table 1 below. Preparation of the composition of Comparative Example 1

[0230] The compositions were prepared as described in Example 1, except that 1244.5 g of deionized water was added in the preparation of the first composition, and no CNTs were added in the preparation of the second composition. The pH of the compositions was about 7.2. Preparation of the composition of Comparative Example 2

[0231] The compositions were prepared as described in Example 4, except that 1483.2 g of deionized water was added in the preparation of the first composition, and no CNTs were added in the preparation of the second composition. The pH of the compositions was about 7.3. Preparation of the Conductive Composition of Comparative Example 3

[0232] The conductive compositions were prepared as described in Example 1, except that 1240.6 g of deionized water was used in the preparation of the first composition and 3.9 g of CNTs was added in the preparation of the second composition. The pH of the conductive compositions was about 7.7. Preparation of the Conductive Composition of Comparative Example 4

[0233] The conductive compositions were prepared as described in Example 1, except that 78.0 g of the copolymer dispersion of Example 1 (7.69 wt.% solids) was added to 2832.0 g of deionized water in the preparation of the first composition, and 90 g of CNTs was added in the preparation of the second composition. The pH of the conductive compositions was about 7.9. Preparation of the Conductive Composition of Comparative Example 5

[0234] A conductive composition was prepared as described in Example 1, except that in the preparation of the first composition, 385.7 g of a 35% sodium polyacrylate solution (obtained from Polysciences Inc., USA) was added to 2600.8 g of deionized water. The pH of the conductive composition was about 7.8. Preparation of the Conductive Composition of Comparative Example 6

[0235] The conductive composition was prepared as described in Example 1, except that in the preparation of the first composition, 135 g of polyacrylamide (obtained from Sigma-Aldrich, Germany) was added to 2851.5 g of deionized water. The pH of the conductive composition was about 7.9. Preparation of the conductive composition of Comparative Example 7 A) Preparation of the copolymer

[0236] The copolymer dispersions were prepared as described in Example 1, except that 30.84 g of sodium hydroxide was added in the preparation of the first suspension, 65.60 g of acrylic acid was added in the preparation of the second suspension, no acrylamide was added in the preparation of the third suspension, and 112.71 g of acrylonitrile was added in the preparation of the fourth suspension. The weight average molecular weight of the copolymer was about 147,000 g / mol, and the solids content of the copolymer dispersion was about 7.87 wt.%. B) Preparation of the Conductive Composition

[0237] A conductive composition was prepared as described in Example 1, except that in the preparation of the first composition, 1715.4 g of the copolymer dispersion of Comparative Example 7 (solids content 7.87 wt.%) was added to 1271.1 g of deionized water. The pH of the conductive composition was about 7.3. Preparation of the Conductive Composition of Comparative Example 8 A) Preparation of the copolymer

[0238] The copolymer dispersions were prepared as described in Example 1, except that 85.45 g of sodium hydroxide was added in the preparation of the first suspension, 164.00 g of acrylic acid was added in the preparation of the second suspension, 53.92 g of acrylamide was added in the preparation of the third suspension, and no acrylonitrile was added in the preparation of the fourth suspension. The weight average molecular weight of the copolymer was about 173,000 g / mol, and the solids content of the copolymer dispersion was about 10.65 wt %. B) Preparation of the Conductive Composition

[0239] A conductive composition was prepared as described in Example 1, except that in the preparation of the first composition, 1267.6 g of the copolymer dispersion of Comparative Example 8 (10.65 wt.% solids) was added to 1718.9 g of deionized water. The pH of the conductive composition was about 7.6. Preparation of Conductive Composition of Comparative Example 9

[0240] The conductive composition was prepared as described in Example 1, except that no sodium hydroxide was added to the fifth suspension in the preparation of the copolymer. The pH of the conductive composition was about 5.4. Preparation of the conductive composition of Comparative Example 10

[0241] The conductive composition was prepared as described in Example 4, except that no sodium hydroxide was added to the fifth suspension in the preparation of the copolymer. The pH of the conductive composition was about 5.1. Preparation of Positive Electrodes of Comparative Examples 1 to 3

[0242] Positive electrodes were prepared in the manner described in Example 1, except that each of the compositions of Comparative Examples 1 to 3 was used in preparing the cathode slurry. Preparation of coin cells of Comparative Examples 1 to 3

[0243] Coin cells were prepared as described in Example 1. Performance measurements of Comparative Examples 1 to 3

[0244] The performance measurements were carried out in the same manner as in Example 1. The performance measurement results of the conductive compositions of Comparative Examples 1 to 3 are shown in Table 1 below. Performance measurements of Comparative Examples 4, 9 to 10

[0245] It was observed that even initially, once milling was complete, it was not possible to produce a well-dispersed conductive composition, so no further performance measurements were made. Performance measurements of Comparative Examples 5 to 8

[0246] It was observed that a stable conductive composition could not be produced, so no further performance measurements were made.

[0247] [Table 1]

Claims

1. A conductive composition comprising a copolymer, carbon nanotubes, and an aqueous solvent, the copolymer comprising a structural unit (a), the structural unit (a) comprising one or more monomer units comprising a cyano group.

2. 2. The conductive composition of claim 1, wherein the proportion of structural unit (a) in the copolymer is from about 20 mol % to about 70 mol %, based on the total moles of monomer units in the copolymer.

3. The conductive composition of claim 1 , wherein the pH of the conductive composition is from about 7 to about 12.

4. 10. The conductive composition of claim 1, wherein the copolymer further comprises a structural unit (b), the structural unit (b) comprising one or more monomer units comprising a carboxylate group.

5. 5. The conductive composition according to claim 4, wherein the proportion of structural unit (b) in the copolymer is from about 10 mol % to about 50 mol %, based on the total number of moles of monomer units in the copolymer.

6. The conductive composition according to claim 1 or 4, wherein the copolymer further comprises a structural unit (c), the structural unit (c) comprising one or more monomer units comprising an amide group.

7. 7. The conductive composition of claim 6, wherein the proportion of structural unit (c) in the copolymer is from about 6 mol % to about 25 mol %, based on the total number of moles of monomer units in the copolymer.

8. 2. The conductive composition of claim 1, wherein the percentage of the copolymer in the conductive composition is from about 4% by weight to about 10% by weight, based on the total weight of the conductive composition.

9. 2. The conductive composition of claim 1, wherein the carbon nanotubes are selected from the group consisting of multi-walled carbon nanotubes, few-walled carbon nanotubes, double-walled carbon nanotubes, single-walled carbon nanotubes, and combinations thereof.

10. The carbon nanotubes have an average diameter of about 0.1 nm to about 100 nm; and the aspect ratio of the carbon nanotubes is about 10 to about 5×10. 6 the BET specific surface area of ​​the carbon nanotubes is about 100 m 2 / g to about 1,500m 2 The conductive composition according to claim 1 , wherein the composition has a molecular weight of 1:1 or more.

11. 2. The conductive composition of claim 1, wherein the percentage of carbon nanotubes in the conductive composition is from about 0.2% by weight to about 3.5% by weight, based on the total weight of the conductive composition.

12. 10. The conductive composition of claim 1, wherein the ratio of the weight of the carbon nanotubes to the weight of the copolymer is from about 1:20 to about 1:

3.

13. 2. The conductive composition of claim 1, wherein the combined percentage of copolymer and carbon material in the conductive composition is from about 4% by weight to about 13% by weight, based on the total weight of the conductive composition.

14. The conductive composition of claim 1 , wherein the aqueous solvent is water.

15. 2. The conductive composition of claim 1, wherein the conductive composition has a viscosity at 20° C. of about 500 mPa·s to about 2,000 mPa·s.

16. An electrode slurry comprising the conductive composition according to claim 1 and an electrode active material.

17. The electrode active material is LiCoO 2 , LiNiO 2 , LiNi 1-x M x O 2 , LiNi x Mn y O 2 , LiCo x Ni y O 2 , Li 1+z Ni x Mn y Co 1-x-y O 2 , LiNi x Co y A z O 2 , LiV 2 O 5 , LiTiS 2 , LiMoS 2 , LiMnO 2 , LiCrO 2 , LiMn 2 O 4 , Li 2 MnO 3 , LiFeO 2 , LiFePO 4 17. The electrode slurry of claim 16, wherein the cathode active material is selected from the group consisting of: and combinations thereof; where each x is independently 0.1 to 0.9; each y is independently 0 to 0.9; each z is independently 0 to 0.4; and M is selected from the group consisting of Co, Mn, Al, Fe, Ti, Ga, Mg, and combinations thereof.

18. The electrode active material is NaCoO 2 , NaFeO 2 , NaNiO 2 , NaCrO 2 , NaVO 2 , NaTiO 2 , NaFePO 4 , Na 3 V 2 (P.O. 4 ) 3 , Na 3 V 2 (P.O. 4 ) 2 F 3 17. The electrode slurry of claim 16, wherein the cathode active material is selected from the group consisting of NMC type mixed oxides, Prussian Blue type sodium compounds, and combinations thereof.

19. The electrode active material is selected from the group consisting of natural graphite fine particles, synthetic graphite fine particles, hard carbon, soft carbon, mesocarbon microbeads (MCMB), Sn fine particles, SnO 2 , SnO, Li 4 Ti 5 O 12 17. The electrode slurry according to claim 16, wherein the anode active material is selected from the group consisting of fine particles, Si fine particles, Si-C composite fine particles, and combinations thereof.

Citation Information

Patent Citations

  • Binder composition for negative electrode, slurry for negative electrode, negative electrode and sodium ion battery

    JP2019079646A

  • Binder aqueous solution for lithium ion battery, slurry for lithium ion battery electrode and manufacturing method therefor, lithium ion battery electrode, and lithium ion battery

    JP2020043064A

  • Conductive carbon material dispersant for lithium ion battery, slurry for lithium ion battery electrode, electrode for lithium ion battery, and lithium ion battery

    JP2021082584A

  • Conductive carbon material dispersing agent for lithium ion battery, slurry for lithium ion battery electrode, electrode for lithium ion battery, and lithium ion battery

    US20210151766A1

  • Binder composition for secondary battery negative electrode, slurry composition for secondary battery negative electrode, secondary battery negative electrode, secondary battery, and method for producing binder composition for secondary battery negat

    WO2012026462A1